eIF6 affects the occurrence and development of esophageal cancer - Cong-Gai Huang; Xin Zhou; Ran Huang; Hui-Ling Zhang; Chen-Xi Li; Fei Du; Hong Lei; Qiong Dai; Zhi-Hui Yang (Molecular Biology Reports, 2026)

Astragaloside IV inhibits the progression of hypertensive heart disease via the RXRA/PPARG/SIRT3 axis - Haoran Jing; Wenjie Cai; Xiaoxue Li; Xin Zhong; Shiyun Dong; Peng Liu; Xi Liu; Ye Jin; Can Wei (Journal of Molecular Medicine, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Sesquiterpenoids isolated from the leaves of Aucklandia costus and their inhibitory effect on nitric oxide production - Long-Gao Xiao; Tao-Bin He; Yan-Xi Li; Yun Niu; Huan Yan; Hui-Ying Liu; Hui Liu; Wei Ni; Xin Fang; Hai-Yang Liu (Phytochemistry, 2026)

AI-enhanced superior bionic skin with dual-layer nanofiber membranes for sweat-based multiple biomarker detection - Xinshuo Liang; Kaisong Huang; Shuo Meng; Wenjie Fang; Shuai Zhang; Leqi Lei; Xin Li; Xi Yao; Jinlian Hu (Chemical Engineering Journal, 2026)

Constructing Co-O-P bridging to induce spin state reconfiguration: In situ electro-oxidation of P for industrial-scale alkaline water electrolysis - Miao Ma; Chuan-De Qi; Qiao Xia; Qian-Xi Lv; Xin-Jie Tian; Man-Man Li; Sheng-Jun Xu; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Bulk nanobubbles do not spontaneously generate radicals but function as field-assisted energy-reducing catalysts - Shuangjian Wang; Zhen Chen; Wengang An; Mingxiao Li; Xin Wang; Wenhao Gao; Wei Fan; Jiangshan Xi; Mingxin Huo (Water Research, 2026)

Two new acylated iridoid glycosides with insulin resistance-improving activity from Scrophularia ningpoensis - Wen-Ying Zhou; Yu-Xin Peng; Bi-Qing Zhao; Hong-Yu Jiang; Xi-Ning Sun; Guang-Yun Su; Li Li; Xiao-Jiang Zhou (Phytochemistry Letters, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Long-term petroleum pollution alters soil microbial communities via electron transfer capacity: Evidence from a 35-year chronosequence - Chengze Yu; Mingxiao Li; Jun Cui; Yanjun Xin; Ran Song; Wangmi Chen; Jiaqi Hou; Jianbing Li; Huibin Du; Beidou Xi (Journal of Environmental Sciences, 2026)

Molecular hydrogen mitigates hydroxyl radical–driven oxidative deterioration of tilapia myofibrillar proteins: through the lens of redox microenvironment modulation - Zhuo-Feng Gan; Jia-Ying Li; Ying-Zhi Yao; Hui-Min Lu; Xi-Yang Chen; Ming-Shen Zhu; Duried Alwazeer; Xin-An Zeng; Lan Liao (Food Chemistry, 2026)

A non-orthogonal state-dependent generalized plasticity model for sand-fine mixtures - Chen-Xi Tong; Xi Liu; Hai-Chao Li; Xin Zhou; Le Wang; Sheng Zhang (Computers and Geotechnics, 2026)

Genetically engineered recombinant thrombin R541W-modified bacterial cellulose for rapid hemostasis and wound repair - Ke Zhang; Lei Xiang; Chihao Zhang; Xi Wu; Changming Chen; Lei Li; Min Xin; Xuefeng Wang; Luhan Bao; Jing Dai (Chemical Engineering Journal, 2026)

A triboelectric sensor array based on facial muscle-action unit-emotion mapping toward astronaut psychological monitoring in long-term missions - Xuyan Hou; Huiyuan Jing; Meiyang Zhang; Fengyan Liu; Ruiwen Zhao; Zhonglai Na; Pingting Zhao; Yuhui Liu; Ximing Zhao; Linbo Xin; Jian Zhou; Xi Chen; et al. (Chemical Engineering Journal, 2026)

High-performance sandwiched pressure sensors enabled by the synergism of multilayer assembly of hierarchical microstructures and interlayer conductivity mismatching - Xue Han; Xi Wang; Huijiang Li; Xiaotian Song; Jinsong Wang; Kaichen Zhang; Lirong Fan; Juanjuan Wang; Xiaopeng Li; Enping Liu; Xiaoli Zhang; Bin Wang; et al. (Chemical Engineering Journal, 2026)

Metal-node coupling of triboelectricity in conductive metal–organic frameworks for contact-electro-catalytic H2O2 generation - Meichen Li; Shuqi Zhou; Yinben Guo; Xueshuang Xiao; Qiqing Xi; Ximing Wang; Xin Han; Qiang Yang (Chemical Engineering Journal, 2026)

Exogenous floc-granule replacement regulates particle-size distribution and signaling-associated ecological responses in aerobic granular sludge - Xin Wang; Yuan Huang; Jie Xu; Bin Lin; Xi Chen; Zhi-Hua Li (Bioresource Technology, 2026)

Radial hydraulic regulation and azimuthal heterogeneity of sap flow in Populus tomentosa: Implications for whole-tree transpiration estimation - Xiaoning Zhao; Kai Wang; Xin Li; Ximeng Li; Brent Clothier; Benye Xi (Agricultural and Forest Meteorology, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Nori and kelp intake attenuates antibiotic-induced gut dysbiosis and resistome expansion - Shilin Hu; Jin-Feng Xi; Tian Liang; Jia-Yang Xu; Ying-Xin Xue; Xin-Wei Yu; Jing-Jing Peng; Hong-Bo Li; Xi-Mei Xue (Journal of Environmental Sciences, 2026)

Nitrogen pulse drives a prolonged microcystin event by increasing the proportion of toxigenic Microcystis genotypes - Jingjing Li; Congmin Wang; Xi Li; Xin Yu (Journal of Hazardous Materials, 2026)

Corrigendum to “DNA methylation mediates the association between organochlorine pesticides and MASLD: An epigenome-wide association study with integrated AOP framework” [J Hazard Mater, 507 (2026) 141727] - Yi Guo; Yutong You; Xin Guan; Yu Yin; Zhen Yin; Guorong Zhong; Chengyong Jia; Yuying Wen; Wenhui Li; Hui Zhao; Shengli Chen; Xi Wang; et al. (Journal of Hazardous Materials, 2026)

The antibiotic resistome in oysters across the Chinese coastline: Enrichment, microbial drivers, and implications for health risk - Huai Lin; Xin Li; Xiaolong Wang; Qingbin Yuan; Fengxia Yang; Wenjin Hu; Xi Li; Liusheng Lei; Yi Luo (Journal of Hazardous Materials, 2026)

In situ Raman insights into amino acid-mineral synergy during methane hydrate nucleation and structural evolution - Jintao Zhuo; Zhendong Luan; Yitong Zhang; Wanying He; Lianfu Li; Shichuan Xi; Zengfeng Du; Xin Zhang (Gas Science and Engineering, 2026)

Effects of functional fermented feed on growth performance, physiological functions, and gut microbiota of Penaeus vannamei - Xin Yu; Na Li; Yulong Zhou; Teng Li; Zeyan Xi; Liwen Liao; Luqing Pan (Animal Feed Science and Technology, 2026)

High-stability active thermal control for nanosatellite payload under multi-timescale disturbances via temperature response decomposition and energy-adaptive error fusion - Qi-Yuan Liu; Yun-Ze Li; Yan-Ao-Ming Xi; Kai-Feng Chang; Ya-Hui Chen; Ran Wei; Yu-Peng Zhou; Xin Zhao (Advances in Space Research, 2026)

Bioactive prenylated acylphloroglucinols from Hypericum scabrum - Li-Ping Teng; Jie-Lian Huang; Shui-Qing Guan; Chen-Xi Xin; Zi-Yin Mai; Yik-Ling Chew; Zhong-Bo Zhou; Gencheng Liang (Natural Product Research, 2026)

Making waves: Harnessing the disinfection byproduct chlorite as an oxidant precursor for micropollutant abatement - Xi Zhang; Yimeng Ma; Mingkai Jia; Wanxin Li; Jiarui Han; Rihui Li; Xin Yang; Ran Yin; Hongqiang Ren (Water Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

CuS-MXene decorated 3D PVA/SA composite aerogels for high-performance solar interfacial water evaporation and desalination - Guoqing Zhang; Weidan Zhao; Dingyu Cui; Xin Xi; Yuliang Zhao; Yingjie Li; Wuxian Zhou; Changqing Huang; Shangzhong Jin; Li Jiang (Journal of Environmental Chemical Engineering, 2026)

Pulsed electric field processing of buffalo milk with retained Joule heating: Microbial efficacy, bioactive protein retention, and flavor profiling - Lang-Hong Wang; Jia-Hong Li; Xu-Rui Li; Yu-Xi Hu; Rui Wang; Xin-An Zeng (Innovative Food Science & Emerging Technologies, 2026)

Identification and comparison of key aroma active compounds in southern and northern sauce-flavor baijiu - Jialiang Niu; Xi Chen; Xin Yao; Weiwei Li; Hua Zhu; Weizheng Sun; Xiuting Li; Baoguo Sun (Food Research International, 2026)

Bioactivity assay coupled with molecular networking for the discovery of antioxidants from purslane - Yan-Xi Li; Mei-Ru Wang; Long-Gao Xiao; Huan Yan; Shan-Shan Ling; Hui Liu; Tao-Bin He; Wei Ni; Xin Fang; Hai-Yang Liu (Food Research International, 2026)

Unraveling the kinetics disparity of hydrothermal Fe/Co-H2O hydrogen production via in situ quantitative monitoring: intrinsic parameters for process scale-up - Shichuan Xi; Zhengcai Zhang; Ruifang Huang; Zhendong Luan; Zengfeng Du; Lianfu Li; Wanying He; Siyu Wang; Yitong Zhang; Nengyou Wu; Xin Zhang (Chemical Engineering Journal, 2026)

Histone lactylation at H4K12 promotes macrophage-fibroblast crosstalk in neodymium oxide-induced pulmonary fibrosis via the PIK3R2/PI3K/Akt/mTOR axis - Wenjie Li; Xi Chen; Yuhang Zhao; Xin Su; Kai Wu; Yi Zhang; Yanhong Dong; Yanrong Gao; Suhua Wang (Chemico-Biological Interactions, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

A novel passive external surface heat flow balance strategy for high-temperature-stability nano CubeSat thermal design: concepts, models and thermal control effect evaluations - Yan-Ao-Ming Xi; Yun-Ze Li; Qi-Yuan Liu; Kai-Feng Chang; Xin Zhao; Yu-Peng Zhou; Ran Wei (Advances in Space Research, 2026)

A novel oral vaccine system for sustainable aquaculture based on live feed diatom: With white spot syndrome virus as an example - Wenting Yang; Shihao Li; Xin Li; Xi Qiang; Xuehua Liu; Songcui Wu; Xiujun Xie; Shan Gao; Guangce Wang (Aquaculture, 2026)

From symptom management to immune prevention: a comprehensive review of chikungunya treatment and vaccine development - Xin Li; Zijun Yuan; Junjie Ni; Dinglei Rao; Wenxian Yin; Xu Wu; Mingxing Li; Fukuan Du; Yueshui Zhao; Jing Shen; Xi He; Chi Hin Cho; et al. (Folia Microbiologica, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Integrative analysis of volatile organic compounds and transcriptional-metabolic networks in two mango cultivars with contrasting aromas - Ying Li; Zixin Lin; Xin Yan; Mina Wang; Xi Pang; Qi Wei; Qing Wang; Bihong Feng (Food Research International, 2026)

Mussel-inspired surface modification for high-rate and effectively complex wastewater systems purification - Minrui Zhan; Xi Zhang; Rong Liu; Manman Zhao; Wenkai Li; Huiyu Yang; Jiehao Du; Wei Chen; Shaojin Gu; Xin Liu; Bin Shang (Desalination, 2026)

Advances and outlook for deep-sea hydrogen detection using in situ Raman spectroscopy - Lianfu Li; Zhendong Luan; Zengfeng Du; Shichuan Xi; Siyu Wang; Wanying He; Zhicheng Wang; Xiaoxiao Guo; Yiyi Jiang; Xin Zhang (Science China Earth Sciences, 2026)

Multifractal dissolved oxygen diagnostics for early warning of aerobic granular sludge destabilization - Lei Chen; Xin Wang; Jia-Hua Yan; Xi Chen; Jian-Dong Hu; Zhi-Hua Li (Water Research, 2026)

A regional classification framework integrating AI and causal inference revealing the drivers of lake eutrophication in China - Yong Xu; Ru-Long Ma; Yu-Xi Feng; Bin Zou; Shen-Xin Li; Wen-Ting Huang; Shang-Chen Zhou; Wen-Qiang Peng (Water Research, 2026)

Unraveling the redox-driven mechanisms of viral-bacterial interactions in modulating the fate of antibiotic resistance genes - Zhurui Tang; Xiaohui Liu; Jiapeng Yang; Fengling Zhang; Xin Shan; Ying Liu; Fengmin Li; Shaoyong Lu; Beidou Xi (Bioresource Technology, 2026)

Emission characteristics and health risk assessment of oil mist and VOCs in several typical industrial processes - DingChao Zhang; Yuying Li; Xin Wang; Kehao Qin; Mengfei Han; Xi Chen; Ziyuan Li; Xin Zhang; Yanling Guan (Journal of Hazardous Materials, 2026)

Operational threshold and associated mechanisms in composting remediation of diesel-contaminated soils - Chengze Yu; Haipeng Huang; Ran Song; Jiaqi Hou; Huibin Du; Mingxiao Li; Yanjun Xin; Beidou Xi (Journal of Environmental Management, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Alternate straw mulching improves sorghum productivity and profitability via moderating soil temperature and conserving moisture in a hot, drought-prone region - Yuzhang Chen; Xin Liu; Songguo Wu; Wei Mo; Min Li; Xi Liu; Licheng Wang; Rui Li; Lijuan Gong (Field Crops Research, 2026)

Enhanced toluene catalytic oxidation over Ag-Cu co-modified Mn2O3: the crucial roles of surface structure reconstruction process - Wei Liu; Shouxin Xin; Xinxin Wang; Yanyan Zhang; Wei Dai; Haiyang Li; Zhongxian Song; Xi Chen; Xuejun Zhang (Environmental Research, 2026)

Serum polychlorinated biphenyls and risk of metabolic dysfunction-associated steatotic liver disease: Cross-sectional and prospective analyses from the Dongfeng-Tongji cohort - Yutong You; Yi Guo; Xin Guan; Guorong Zhong; Yu Yin; Zhen Yin; Yuying Wen; Wenhui Li; Hui Zhao; Shengli Chen; Chengyong Jia; Xi Wang; et al. (Environmental Pollution, 2026)

Optimizing the keratin degradation activity of keratinase via in silico and molecular engineering approaches - Yu-Xin Chen; Xiang-Lan Xi; Chang Su; Meng-Ting Tan; Heng Li; Jin-Song Gong; Zheng-Hong Xu; Jin-Song Shi (Systems Microbiology and Biomanufacturing, 2026)

CHiC gene positively regulates the resistance to Botrytis cinerea in Arabidopsis - Xi Wu; Xin Yu; Shuxun Xu; Shuangyao Li; Jing Zhang; Guangna Chen; Qian Ma; Shuqing Cao; Hui Song (Plant Cell Reports, 2026)

Magma oxygen fugacity controls the mineralization of magmatic Cu-Ni sulfide deposits in orogenic belts: Insights from the Baixintan and Haibaotan intrusions, Eastern Tianshan, NW China - Tao Zheng; Yuping Su; Jianping Zheng; Jian Wang; Xin Li; Pengbing Li; Xiao Bian; Ke Geng; Xi Chen; Ying Wei (Lithos, 2026)

Dose and food matrix effects on selenium retention in mouse tissues from selenium-rich vegetables and rice: Implications for selenium bioavailability - Jin-Feng Xi; Xin-Ying Lin; Ning Wang; Jin-Lei Yang; Dongmei Zhou; Hong-Bo Li (Journal of Trace Elements in Medicine and Biology, 2026)

Redox-active co-pyrolytic carbon enhances electron transfer and mitigates petroleum hydrocarbon hazards in contaminated soils - Chengze Yu; Haipeng Huang; Ran Song; Jiaqi Hou; Huibin Du; Mingxiao Li; Yanjun Xin; Beidou Xi (Journal of Hazardous Materials, 2026)

DNA methylation mediates the association between organochlorine pesticides and MASLD: An epigenome-wide association study with integrated AOP framework - Yi Guo; Yutong You; Xin Guan; Yu Yin; Zhen Yin; Guorong Zhong; Chengyong Jia; Yuying Wen; Wenhui Li; Hui Zhao; Shengli Chen; Xi Wang; et al. (Journal of Hazardous Materials, 2026)

Ecological effect of China's 30-year National Garden City policy: Synergistic acceleration of urban greening, carbon sequestration, and biodiversity - Longqin Li; Wenbin Xu; Haorui Wu; Yisu Zhang; Xi Chen; Longjin Dai; Xin Wang; Weiqing Meng; Hongyuan Li (Environmental Impact Assessment Review, 2026)

From apparent equilibrium to limiting state: Adsorbed phase density kinetics of supercritical methane and its implications for adsorption-diffusion in deep coalbed reservoirs - Tengfei Jia; Songhang Zhang; Meng Wang; Shuheng Tang; Yanming Zhu; Sijian Zheng; Zhaodong Xi; Qian Zhang; Di Xin; Feng Qiu; Jianxin Li (Chemical Engineering Journal, 2026)

Conservation genomics highlights the urgency of protecting Indo-Pacific humpback dolphins (Sousa chinensis) in Chinese waters - Xin Huang; Xiyang Zhang; Liyuan Zhao; Guixin Dong; Wenliang Zhou; Dengfeng Guan; Guiqiang Wang; Zhenhui Xie; Fei Liu; Chaoming Zhang; Xi Chen; Songhai Li; et al. (Science China Life Sciences, 2026)

Two subtropical mycorrhizal tree species differ in contributions to soil carbon pools under drought - Juan Wang; Mengyang Deng; Yanyan Bian; Yi Li; Sarita Keski-Saari; Qingpei Yang; Jun Liu; Fenggang Luan; Qingni Song; Xin Xiong; Dan Xi; Xiong Fang (Plant and Soil, 2026)

Medication association analysis of antimicrobial-induced arrhythmias based on FP-growth frequent pattern mining - Shuang Chai; Li Deng; Jie Dong; Jiaxu Zhou; Xin Xi; Guili Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Pyroptosis as a double-edged sword in colorectal cancer: Molecular mechanisms and therapeutic opportunities - Han-Xi Zhang; Wen-Jing Xu; Yi-Xin Jiang; Lu Li; Bai-Yu Chen; Meng-Yao Cheng; Meng-Yuan Hao; Hang-Shen Han; Hong-Jie Li; Yan-Ge Li; Dong-Dong Wu (Apoptosis, 2026)

A plasticity-aware machine learning framework for genomic prediction and resource-efficient wheat breeding under multi-environment conditions - Lei Li; Cong Zhao; Huihui Li; Xi Tian; Jindong Liu; Duoxia Wang; Keyi Wang; Shuaipeng Fei; Guoliang Wan; Jianqi Zeng; Yachao Dong; Jixin Li; et al. (Computers and Electronics in Agriculture, 2026)

Storage time drives divergent microbial functions and flavor metabolism in high-temperature Daqu - Xin Yao; Xi Chen; Jialiang Niu; Jinyang Li; Weiwei Li; Hua Zhu; Xiuting Li; Baoguo Sun (Food Research International, 2026)

Alleviating effects and mechanism of Lacticaseibacillus paracasei BHP06 on the allergic reactions induced by ovalbumin - Xiang-Ge Xin; Yue Meng; Jun Meng; Jun Xi; Chang-He Ding; Rui-Han Ge; Yu-Tong Bai; Ming-He Li (Food Bioscience, 2026)

Enzymatic routes to initiator-based functional biodegradable polyesters - Yu Zhang; Ya Cai; Yihuan Liu; Li Xi; Xin Hu; Kai Guo; Ning Zhu (Chemical Engineering Journal, 2026)

Synergetic enhancement of bandgap, polarization, and glass transition in polyimide copolymers for high-temperature energy storage - Shuxuan Li; Xi Chen; Bo Liu; Xin Zhen; Aidi Zhang; Bei Li; Xin Zhang (Chemical Engineering Journal, 2026)

Flash joule heating-induced synthesis of biowaste-derived metal-free catalysts for nitrate reduction reaction - Xin Chen; Zhaoyu Wang; Liuhong Yang; Runmiao Yuan; Shuyi Huang; Qinyuan Hu; Xue Wang; Cong Gu; Xiangli Wen; Xi Chen; Hongji Zhang; Dongjian Shi; et al. (Bioresource Technology, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Akkermansia muciniphila enhances the antitumour efficacy of αPD-1 therapy in gastric cancer by remodelling the tumour immune microenvironment - Ziyi Yang; Lanfan Liang; Xin Li; Xizhen Peng; Xinyi Qian; Zehua Huang; Xi Wang; Qing Hu; Xiangsheng Fu (Toxicology and Applied Pharmacology, 2026)

Migrion: a Migrasome-mediated unit for intercellular viral transmission - Yuxing Huang; Xiaojie Yan; Xing Liu; Congcong Ji; Wenmin Tian; Haohao Tang; Yong Li; Yiling Wen; Peiyao Fan; Hongli Wang; Cankun Xi; Zhongtian Li; et al. (Science Bulletin, 2026)

Onset timing and palaeoenvironmental records of Carnian Pluvial Episode (Late Triassic) in southwestern Guizhou, China - Shi-Xin Li; Zhi-Heng Ma; Xi Zhang; Wei Yang; Jian-Li Zeng; Mihai Emilian Popa; Kai-Nan Mao; Ting-Shan Zhang (Palaeoworld, 2026)

ClO2 fumigation of yam tubers prior to storage inhibits enzymatic Browning in fresh-cut yams: impact of ClO2 on phenylpropanoid metabolism and membrane integrity - Zixin Lin; Rongchun Yao; Xi Pang; Huafeng Liang; Ying Li; Xianxin Wu; Xin Yan; Shuzhi Yuan; Xiaodi Xu; Aili Jiang; Bihong Feng; Xiaozhen Yue; et al. (Food Chemistry, 2026)

Cadophorin C, a new cyclic heptapeptide isolated from a mangrove-derived fungus Penicillium sp. GXIMD 03101 - Jia-Li He; Xiao-Dong Jiang; Yu-Man Gan; Xin-Jian Qu; Xiang-Xi Yi; Yong-Hong Liu; Cheng-Hai Gao; Meng Bai (Natural Product Research, 2026)

Natural variation in VrERF088 modulates drought tolerance during mungbean germination - Xi Zhang; Jinyang Liu; Shicong Li; Yun Lin; Yixiang Pu; Qiang Yan; Jingbin Chen; Ranran Wu; Na Yuan; Prakit Somta; Lixia Wang; Xin Chen; et al. (Theoretical and Applied Genetics, 2026)

RNA immunity: an ancient defense mechanism preserved in mammalian cells - Zheng Fu; Liang Li; Yanbo Wang; Xin Yin; Xi Chen; Chao Yan; Dangsheng Li; Chen-Yu Zhang (Science Bulletin, 2026)

Precision screening of Lactobacillus with potential anti-allergenic using dual cell model - Xiang-Ge Xin; Yue Meng; Zai-Chen Li; Jun Xi; Jun Meng; Chang-He Ding; Dong-Ge Zheng; Ling-Guang Du; Shu-Song Wang (Food Bioscience, 2026)

Efficient photocatalytic conversion of air into nitrate over 2D ultrathin WO3 promoted by Ru nanoclusters and oxygen vacancies synergistically - Feng Ding; Peng Chen; Xin Li; Xu Li; Wenhao Xi; Yuan Feng; Miaomiao Liu; Jia Li; Xidong Duan (Chemical Engineering Journal, 2026)

Design of lignin-derived elastic gradient-pore biocarbon with enhanced interfacial effects for supercapacitor applications - Xi Guan; Lili Zhang; Xin Li; Hailong Lu; Zhiguo Wang; Jinxia Ma; Yonghao Ni (Chemical Engineering Journal, 2026)

Cu-modified Co3O4-MnO2 interfaces enable sustained lattice oxygen activation for catalytic toluene mineralization - Wei Liu; Xinxin Wang; Junmin Li; Shouxin Xin; Yanyan Zhang; Haiyang Li; Xu Zhang; Wei Dai; Jiaxin Geng; Zhongxian Song; Xi Chen; Xuejun Zhang (Chemical Engineering Journal, 2026)

Development and validation of a multiplex high-risk HPV detection method using lyophilized microsphere technology and multicolor melting curve analysis - Miao Fu; Huabin Wang; Yingchao Wu; Chaoyong He; Wei Chen; Na Zhang; Xin Chen; Jinhua Wang; Xiaohuan Zhao; Meili Lin; SiSi Mao; Xi Xiang; et al. (Chemical Engineering Journal, 2026)

Soil moisture dynamics and rainfall infiltration across vegetation types in subtropical ecosystems in Southwest China - Qiao-Shun Yan; Yu-Xi Peng; Xiao-Jin Jiang; Pei-Li Fu; Zhi-Yun Lu; Xiao-Wen Hu; Yong-Jiang Zhang; Jiao-Lin Zhang; Ze-Xin Fan (CATENA, 2026)

FRET-based colorimetric and ratiometric fluorescent probe for Hg2+ detection in water, soil, plants and live cells - Yuanyuan Zhang; Xi Zuo; Yujing Li; Ruobo Shi; Xin Hu; Zhongliang Liu; Zheyu Zhang (Analytica Chimica Acta, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

In-situ construction of a green and recyclable ZnS-modified ZnO/carbon xerogel from pulping black liquor for sustainable pollutant purification - Xi Guan; Xin Li; Zhiguo Wang; Jinxia Ma; Lili Zhang (Journal of Cleaner Production, 2025)

Health risk and benefit assessment methods for antibiotic resistance bacteria/genes in the environment: A critical review - Wenling Chen; Lihua Li; Xi Dai; Lin Feng; Xin Yu (Journal of Environmental Management, 2025)

Recovering carbon fibers from waste carbon fiber reinforced polymer composites via electrified Joule heating-assisted pyrolysis - Ming-xin Xu; Jie Yang; Xiang-xi Meng; Jun-ping Zhang; Yi-ye Lu; Ya-chang Wu; Wei Li; Qiang Lu (Journal of Environmental Sciences, 2025)

Dietary prebiotics combined with iron supplementation: A two-pronged approach to reduce rice cadmium bioavailability - Rong-Yue Xue; Yao-Sheng Zhang; Jin-Feng Xi; Lei Zhou; Xin-Ying Lin; Tian-Wen Ye; Yu-Hang Bao; Dongmei Zhou; Hong-Bo Li (Food and Chemical Toxicology, 2025)

Pan-genomic insights into RLK family evolution and adaptation in Dioscorea alata - Zhi-Yan Wei; Sai-Xi Li; Ming-Han Li; Jie Tang; Yu-Qian Jiang; Xin-Yu Lu; Yan-Mei Zhang; Jia-Yu Xue (Plant Molecular Biology, 2025)

Hippocampal Extracellular Matrix Protein Laminin β1 Regulates Neuropathic Pain and Pain-Related Cognitive Impairment - Ying-Chun Li; Pei-Yang Liu; Hai-Tao Li; Shuai Wang; Yun-Xin Shi; Zhen-Zhen Li; Wen-Guang Chu; Xia Li; Wan-Neng Liu; Xing-Xing Zheng; Fei Wang; Wen-Juan Han; et al. (Neuroscience Bulletin, 2025)

Enhanced production of eicosapentaenoic acid and fucoxanthin in Phaeodactylum tricornutum via a two-stage strategy with multifactorial synergistic effects - Xin Dong; Meng-Han Zhao; Chen-Xi Li; Xiao Lin; Ning Ma; Hong-Jin Qiao; Dian-Feng Han; Ying-Jiang Xu (Journal of Applied Phycology, 2025)

Effect of Scale-Dependent Particle Morphology on the Single-Particle Crushing Behavior of Granular Soil - Chen-Xi Tong; Xin-Ji-Yuan Li; Zong-Lei Dong; Sheng Zhang; Daichao Sheng (Transportation Geotechnics, 2025)

Dynamic response of a continuous rigid-frame bridge under potential landslide-induced surges - Kai Zhou; Jiajia Wang; Lili Xiao; Tiantian Li; Xin Xu; Zhiqiang Li; Xi Yu (Ocean Engineering, 2025)

Design and characterisation of the out-of-plane dielectric elastomer generator for wave energy harvesting - Xi Wang; Jinxin Wang; Tianyou Zhang; Jung-Che Chang; Siqian Li; Yao Zhang; Tianyi Zeng; Xin Dong (Ocean Engineering, 2025)

The potential of anthraquinone-2-sulfonate (AQS) for “shell breaking” of iron-coated denitrification granular sludge - Xin-Rui Zhang; Zhi-Han Xi; Zi-Jun Yan; Xin-Tao Liu; Ying Wang; Run-Mei Li; Zi-Yue Li; Ke-Yu Wu; Ren-Cun Jin; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Management, 2025)

Assessing the effect of composted cyclosporin A fermentation residue as organic fertilizer: Focus on soil fertility and antibiotic resistance - Dong Wang; Xiang Chen; Xiaofen Li; Qingwen Zhang; Jiaqi Hou; Yuefei Li; Beidou Xi; Zhihao Sun; Shuaishuai Xin; Guocheng Liu; Huiling Liu; Yanjun Xin (Journal of Environmental Sciences, 2025)

Climate-driven expansion of Takayama acrotrocha blooms: First outbreak along the north coast of Shandong, China linked to intense precipitation and warming - Xin Hong; Zheng-Xi Zhou; Jin-Xiu Wang; Chao Liu; Hui-Xia Geng; Yi-Jia Song; Yi-Fan Li; Fan-Zhou Kong; Qing-Chun Zhang; Ren-Cheng Yu (Environmental Pollution, 2025)

Characterization and source analysis of VOCs and PM2.5 species in Lanzhou, northwestern China in 2017–2021: Implications for pollution control strategies - Xi Zhou; Zhongqin Li; Feiteng Wang; Zhizhong Zhao; Shichang Kang; Junhua Yang; Yunhua Chang; Dunsheng Xia; Kaiming Li; Xin Zhang; Fanglong Wang; Mengyang Fang (Environmental Pollution, 2025)

An innovative and clean strategy to recover copper resources from waste printed circuit boards: Malic acid leaching and micro-nano copper preparation - Xi-guang Li; Xin-long Li; Guang-liang Wei; Jing-tao Chen; Xiao-tian Zhao; Chun-chen Nie; Lin Li; Shuai Yan; Xiang-nan Zhu (Chemical Engineering Journal, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Mechanistic insights into water use strategies and heat tolerance of Australian native trees in saline soils: Implications for phytoremediation under climate change - Xi Sun; Jie Li; Mohammad Saberian; Gang Ren; Xin Liu; You Gao (Plant and Soil, 2025)
Aims This study evaluates the water use strategies and physiological resilience of three Australian native tree species in saline soils to assess their potential for phytoremediation under climate change. We hypothesise that species with high water demand and delayed stomatal closure under aridity can enhance soil salinity mitigation through sustained transpiration and groundwater regulation. Methods Continuous sap flow measurements were recorded over 12 months on nine trees (three per species) from three species across three moderately saline sites in Melbourne, Australia. Detailed analyses of morphological traits, sapwood properties, and soil profiles (including texture and water content) were conducted. Diurnal sap flow patterns, peak flow timing, and physiological responses to temperature and vapour pressure deficit (VPD) were evaluated to determine species-specific thresholds for heat and drought tolerance. Results Melaleuca styphelioides exhibited the highest water use, consuming 128% and 97% more water monthly than Lophostemon confertus and Corymbia maculata , respectively. Its peak sap flow occurred later in the day (15:00–17:00), coinciding with sustained stomatal conductance under high VPD (1.9–2.0 kPa) and extreme temperatures (41 °C). Optimal physiological performance for this species occurred at higher temperatures (32.2–33.4 °C) and VPD (1.9–2.0 kPa). Conclusions Melaleuca styphelioides may warrant further investigation as a potential candidate for water management in saline environments, given its higher water consumption and ability to maintain sap flow under elevated temperature and VPD conditions. These findings suggest that additional research, incorporating larger sample sizes and direct measurements of soil salinity changes, would be valuable to evaluate the suitability of this species for phytoremediation applications in aridifying regions.

Middle Campanian to Maastrichtian foraminifera and biomarkers: Seawater incursion events in the Songliao Basin, Northeast China - Ke-Ying Yue; Sha Li; Tian Jiang; Dang-Peng Xi; Bo-Wen Song; Yu Liang; Li-Xin Sun; Tian-Fu Zhang; Hai-Chun Zhang; Xiao-Qiao Wan; Bo Wang (Palaeoworld, 2025)

Real-time tracking of cysteine dynamics in living cells and mice using a NIR fluorescent probe: Implications for environmental oxidative stress assessment - Wen-Yu Lu; Zi-Hao Chen; Xi-Xi Wu; Xian-Dong Zhang; Xin-Yue Li; Hui-Jing Li; Jun-Hu Wang; Yan-Chao Wu (Journal of Environmental Chemical Engineering, 2025)

Unveiling the interface effects at CuO-Co3O4 heterostructures on low temperature degradation of toluene - Wei Liu; Shouxin Xin; Huiqiong Yu; Xinxin Wang; Yanyan Zhang; Wei Dai; Haiyang Li; Zhongxian Song; Xi Chen; Xuejun Zhang (Journal of Environmental Chemical Engineering, 2025)

Key problems in refractory pollutants degradation by geopolymers based on mine tailings waste: From synthesis to application - Chaoqun Zhu; Yinghua Li; Xin Guo; Kun Wang; Wanqi Li; Junxiang Wang; Mingchuan Zhang; Xi Chen (Journal of Environmental Chemical Engineering, 2025)

Particulate matter removal performance of basalt fiber fabric: Optimization on the textile structure and surface functionalization - Ming-Cheng Gao; Ting Zhao; Hui Li; Cun-Guang Liang; Xiao-Xi Cheng; Xin Jia; Peng-Cheng Ma (Journal of Environmental Chemical Engineering, 2025)

Assessment of gas fluxes from Yokosuka hydrothermal field in the western Pacific Ocean based on in situ observations - Lianfu Li; Peiwen Zhang; Lei Xing; Zhenhua Xu; Zhendong Luan; Zengfeng Du; Shichuan Xi; Siyu Wang; Wanying He; Xin Zhang (Global and Planetary Change, 2025)

Mitochondrial DNA leakage and micronucleus formation activate the cGAS–STING pathway in aristolochic acid I-induced nephritis - Yu yang Lei; Yu shi Hu; Yi yi Cao; Jing Xi; Yu ning Ma; Xiao hong Zhang; Qin wen Gao; Ji an Fu; Xin yu Zhang; Li Su; Yang Luan (Food and Chemical Toxicology, 2025)

Serum polychlorinated biphenyl levels and risk of incident chronic kidney disease: A prospective study in the Dongfeng-Tongji cohort - Sijie Chai; Yutong You; Yi Guo; Xin Guan; Guorong Zhong; Zhen Yin; Yu Yin; Yuying Wen; Wenhui Li; Hui Zhao; Shengli Chen; Xi Wang; et al. (Environmental Pollution, 2025)

3D PVA/CNFs/MXene aerogel-based evaporator with anti-biofouling and salt-resistant for efficient solar steam generation and wastewater purification - Wangwei Pan; Weidan Zhao; Denghao Li; Mi Liu; Guoqing Zhang; Xin Xi; Li Jiang (Desalination, 2025)

Wood-derived carbon as self-supporting cathode and current collector for static zinc-iodine batteries - Xinyue Zheng; Hongjie Shen; Junjie Wei; Wenkai Chen; Xi Chen; Shipeng Li; Xin Zheng; Sai Wu; Yajun Pang; Hao Chen (Bioresource Technology, 2025)

Chemotaxonomic significance of chemical constituents from Ligia exotica, sea slater - Yue-Yao Li; Fei-Hua Yao; Qian Han; Jin-Li Luo; Xin-Yue Li; Cheng-Hai Gao; Xiang-Xi Yi (Biochemical Systematics and Ecology, 2025)

Tidal modulation and temporal dynamics of methane emissions at the Formosa Ridge: insights from in-situ observations - Xiong Zhang; Zhendong Luan; Zengfeng Du; Lianfu Li; Shichuan Xi; Chao Lian; Xin Zhang (Frontiers in Marine Science, 2025)
Methane emissions from cold seeps play an important role in oceanic carbon cycling and climate regulation, yet their temporal dynamics and controlling mechanisms remain poorly understood. We conducted long-term in situ monitoring at the Formosa Ridge (Site F), southwest of Taiwan, using a self-developed ocean observation platform that integrates an acoustic Doppler current profiler (ADCP), conductivity–temperature–depth (CTD) sensors, current meters, and other instruments, enabling multi-parameter correlation analysis. The observations revealed pronounced temporal variability in gas emissions, with emission intensity closely correlated with bottom pressure fluctuations controlled by tidal cycles. The results suggest that hydrostatic pressure changes promote or inhibit hydraulic fracturing, thereby modulating gas release. These findings support a conceptual model of the seep’s fluid system, characterized by a constant subsurface methane supply and tidally modulated episodic bubble discharge, a mechanism likely applicable to other cold seep environments globally and offering new insights into the dynamics of marine methane emissions.

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Exploring Allium mongolicum Regel flavonoids alleviation of deoxynivalenol-induced gut inflammation and flesh-quality improvement based on muscle-intestinal axis in a Channa argus model - Zhe Yu; Zhuang Xiong; Yi Wang; Zhi-Qiang Gao; Ke-Xin Lu; Ying Zhang; Mu-Yang Li; Yuan-Xi Yue (Food Bioscience, 2025)

Deciphering ion-specific synergy: Al3+/Zn2+ orchestrated cellulose-copolymer interfacial engineering for all-weather wearable electronics - Xin Li; Huicong Jiang; Qianqian Jia; Xi Guan; Ming Yan; Lili Zhang; Juan Yu; Jinxia Ma; Chuanwei Lu; Zhiguo Wang (Chemical Engineering Journal, 2025)

Association of GRM7 Polymorphisms with Bilateral Auditory Regions Glutamate and Coupling with Glutathione in ARHL Patients - Jing Wang; Fuyan Li; Fuxin Ren; Wen Ma; Yuxi Liu; Wenjing Zhang; Xi Li; Yanfei Bi; Qian Xin; Fei Gao (Molecular Neurobiology, 2025)

Assessing the short-term exposure risk and mortality burden of dust and fine aerosol PM2.5 in Central Asia - Xinzhu Li; Shan Zhou; Xin Xi (Science of The Total Environment, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Large hydrogen hydrothermal pipe swarm identified in the deep ocean - Lianfu Li; Hongyun Zhang; Shichuan Xi; Chenglong Liu; Congying Li; Jian Zheng; Jing Huang; Yufei Hao; Xin Zhang; Weidong Sun (Science Bulletin, 2025)

A five-chamber parallel microbial demineralized fuel cell for removal of microplastics from mine water: Effects, performance, and microbial communities - Lifeng Shi; Xin Li; Yukuo Liu; Xi He; Lin Liu; Xuejing Liu; Fuping Li; Hao Wang (Journal of Environmental Chemical Engineering, 2025)

Isolation and identification of toxins inhibiting Shal potassium channels from the venom of Ornithoctonus hainana spider - Minzhi Chen; Li Yang; Guo Zeng; Xin Xiao; Zhonghua Liu; Gaihua Zhang; Xi Zhou (Toxicology and Applied Pharmacology, 2025)

Environmental drivers and microbial interactions in harmful dinoflagellate blooms: Insights from metagenomics and machine learning - Kuidong Zhang; Mansong Xi; Guimei Wu; Feimiao Lu; Guichun Wu; Jun Zhou; Jie Zhang; Xin Wang; Yanzhao Li; Cile Xu; Mengxuan Yang; Hongxia Wang; et al. (Process Safety and Environmental Protection, 2025)

A new insight into the mechanism of cadmium-induced nephrotoxicity and antagonism of selenium nanoparticles: modulation of MTF1-MT axis dependent metal homeostasis - Yi-Xi Tang; Hui-Lin Cao; Jia-Rong Hou; Jian Chen; Shi-Yong Zhu; Yun-Shuang Liang; Zhou-Yi Yang; Kanwar Kumar Malhi; Xin-Yue Mao; Jin-Long Li (Environmental Pollution, 2025)

Ketamine Alters Specific Gene Expression Profiles by Transcriptome-Wide Responses in a Ketamine-Induced Schizophrenia-Like Mouse Model - Zhe Du; Xiu-mei Zhu; Peng Lv; Ying Pan; Xi-kai Hou; Ang Li; Dong Zhao; Jia-xin Xing; Jun Yao (Molecular Neurobiology, 2025)

Comprehensive assessment of 45 antibiotics in ten urban wastewater treatment plants in Northeastern China: Terminal treatment is not a reliable guard - Xin-Ming Guo; Xi-Mei Lu; Jing-Wen Jia; De-Feng Xing; Yi-Fan Li; Guang-Li Cao; Zi-Feng Zhang (Journal of Hazardous Materials, 2025)

Mechanistic analysis of urban tree-soil interactions: Species-specific water use and desiccation effects on expansive clays - Xi Sun; Jie Li; Xin Liu; Shengshen Wu; You Gao (Plant and Soil, 2025)
Aims This study investigates the complex interactions between urban trees and expansive clay soils, focusing on two prevalent species ( Corymbia maculata and Lophostemon confertus ) in Melbourne’s urban landscape. Limited field data and understanding of species-specific water use necessitate this research. We aim to quantify the spatiotemporal variability in soil-plant-water interactions within the urban contexts, a crucial factor for informed green infrastructure planning and sustainable ecosystem management in metropolitan areas. Methods Comprehensive field measurements were conducted over 12 months, including soil movement, soil water dynamics, tree transpiration, and leaf water potential. Sap flow sensors monitored tree water requirements. Laboratory soil testing determined soil properties and developed soil suction and water content profiles. The intercorrelation between soil water dynamics and tree water use was investigated. Results Peak water use for both trees occurred during summer, contributing 32–40% of their total consumption. C. maculata transpired 48.1 kL, exceeding L. confertus by 106%. The trees’ desiccation influence extended horizontally to 0.4–0.5 times the tree height and vertically to 2.3–3.3 m depth. Soil water content explained 31–36% of soil movement variability, with a strong correlation (R² > 0.9) between soil suction and water content within the active root zone. Conclusions This study enhances our mechanistic understanding of urban tree-soil interactions, providing valuable insights for sustainable city planning. It emphasizes species-specific considerations in tree selection and placement, especially in areas with expansive soils. The robust field data contributes to refining predictive models of soil-plant-atmosphere interactions in urban landscapes, supporting informed decision-making in urban greening initiatives.

Methane Adsorption Capacity of Deep Buried Coal Seam Based on Full-Scale Pore Structure - Qian Zhang; Shuheng Tang; Songhang Zhang; Zhaodong Xi; Di Xin; Tengfei Jia; Xiongxiong Yang; Ke Zhang; Jianxin Li; Zhizhen Wang (Natural Resources Research, 2025)

Differences of Morphology and Muscle Transcriptomes Reveal the Individual Difference of Swimming Performance in Juvenile Spotted Sea Bass (Lateolabrax maculatus) - Haoyang Li; Hao Li; Chengtian Li; Xi Jin; Weiwei Li; Haishen Wen; Yun Li; Qianyan Lai; Chunxiang Niu; Xin Qi (Journal of Ocean University of China, 2025)

Thermal death kinetics of pests in tobacco leaves as influenced by heating rates and life stages - Jinsong Zhang; Xin Ye; Zijun Mo; Hongwei Wang; Xican Gu; Jiaqin Xi; Rui Li; Shaojin Wang (Journal of Stored Products Research, 2025)

Unraveling the impact of micro- and nano-sized polymethyl methacrylate on gut microbiota and liver lipid metabolism: Insights from oral exposure studies - Peng Chen Zheng; Xin Qiang Pan; Yi Jiong Zhou; Keng Po Lai; Rong Li; Xiao Xi Zhang (Environmental Pollution, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Bacterial assemblies in acidic dryland vs. paddy soils across depth profiles in southern China's red soil region - Xin Li; Yun Ge; Fangjing Hu; Yongxiu Qi; Lingzhi Li; Xu Chen; Xi-En Long (Pedobiologia, 2025)

World's largest oligotrophic Lake Baikal: Concerns about cyanobacterial blooms and potential microcystin producers along the littoral zone - Xi Li; Irina V. Tikhonova; Sergey A. Potapov; Andrey Yu. Krasnopeev; Natalya A. Zhuchenko; Xin Niao; Lin Wang; Ekaterina G. Sorokovikova; Weixuan Wang; Olga I. Belykh (Harmful Algae, 2025)

Enhanced methane production through synergistic integration of quorum sensing Signals and microbial electrolysis in anaerobic digestion of low-quality biomass - Xiayuan Wu; Shen Wang; Wanqi Zhao; Yonglan Xi; Shuhuan Li; Fengxue Xin; Weiliang Dong; Honghua Jia (Bioresource Technology, 2025)

Intravenous immunoglobulin ameliorates doxorubicin-induced intestinal mucositis by inhibiting the Syk/PI3K/Akt axis and ferroptosis - Xiaochen Yan; Peng Jiang; Changqing Li; Fengjuan Liu; Ping Fu; Dengqun Liu; Xi Du; Li Ma; Tong Wang; Xin Yuan; Shengliang Ye; Zongkui Wang (Apoptosis, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

The antinociceptive and anti-alpha-glucosidase effects of glucosides from Hemiphragma heterophyllum Wall. - Chun-Fang Wen; Yu-Xiao Li; Ke-Xin Nie; Qiu He; Ya Lu; Zi-Liang Wang; Xi-Shan Bai; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2025)

Reconstruction of 2‐m Air Temperature From ERA5 Reanalysis at Dome A, Antarctica - Yifan Wu; Yu Jiang; Yi Zhang; Yichen Li; Xin Chen; Wenqian Zhang; Xi Zhao (International Journal of Climatology, 2025)
In this study, we jointly used in situ air temperature from AWS and reanalysis data from ERA5 to make the first‐ever reconstruction of a 42‐year (1978–2020) air temperature time series for Dome A, Antarctica. By analysing the impact of environmental variables, we found that the 10‐m u‐component of wind was the predominant one for air temperature bias between ERA5 and AWS, followed by total cloud cover. Air temperature deviations between ERA5 and AWS during the period of 2005–2020 were successfully reduced by applying a random forest (RF) model, decreasing the bias by 0.52°C, the RMSE by 3.16°C and the MAE by 2.77°C. We next applied the RF model to predict the 2‐m air temperature difference which was added back to correct ERA5 from 1978 to 2004. This yielded an accurate time series of air temperature from 1978 to 2020. Using the innovative trend analysis method to analyse the temperature trend of the corrected data, we found that Dome A has experienced a gradual warming of 0.10°C dec −1 over the 42‐year period. Among the seasonal temperature changes, spring showed a significant warming trend of 0.57°C dec −1 , autumn and winter showed no significant warming, while summer showed a slightly cooling trend. Also, over the 42‐year analysis period, a stable oscillation period of ~28 year was observed. This cycle emerged as the dominant pattern, influencing the overall temperature evolution. The method proposed in this research, which combines machine learning with AWS to correct ERA5 air temperature data, holds the potential to address spurious changes of reanalysis data in long‐time series studies, thus improving the reliability of trend analyses.

Probiotic potential of intestinal bacteria isolated from the digestive tract of hybrid snakehead (Channa argus♀ × Channa maculata♂) - Wen-Hao Wu; Yan-Xin Sun; Jia-Hao Zhang; Kun-Ming Huang; Xi-Chao Liu; Shu Tang; Wei Li; Biao Jiang; You-Lu Su (Aquaculture, 2025)

R-spondin1 plays an indispensable role in ovarian development of Qi River crucian carp (Carassius auratus) by regulating estrogen synthesis - Limin Wu; Mengfan Wu; Yongjing Li; Qingqing Xin; Yuchi Wang; Xi Shi; Xuejun Li (Theriogenology, 2025)

Surface electron transfer promoted by Peroxymonosulfate oxidant enhances bioleaching of arsenic-containing gold ore - Jiayu Xin; Jiahong Li; Xi Zhao; Changliu He; Lei Zheng; Aijun Zhang; Ranting Tao; Xu Zhang (Minerals Engineering, 2025)

Genomic analysis of Vreelandella sp. F11 reveals its role in alginate utilization - Xin-Xiao Qu; Yu-Qi Zhang; Fei-Yu He; Xi-Ying Zhang; Peng Wang; Fei Xu; Yu-Qiang Zhang; Long-Sheng Zhao; Ping-Yi Li; Fang Zhao (Marine Genomics, 2025)

Peficitinib suppresses diffuse-type tenosynovial giant cell tumor by targeting TYK2 and JAK/STAT signaling - Shan Lu; Chenxi Cao; Wenjia Zhang; Jiayi Li; Jingli Yang; Zisheng Huang; Zhijun Wu; Baitao Liu; Hongjie Huang; Haijun Wang; Yongjian Wang; Dingge Liu; et al. (Science China Life Sciences, 2025)

Spinal PTP1B Regulated NMDA Receptor-mediated Nociceptive Transmission and Peripheral Inflammation-induced Pain Sensitization - Shu-Jin Wu; Xin-Yi Lan; Yue Shi; Yan-Ni Liu; Xiao-Xi Zhang; Qi Zhang; Yu-Bo Gao; Juan Li; Xian Yang; Hu-Hu Bai (Molecular Neurobiology, 2025)

17β-Trenbolone Exposure Enhances Muscle Activity and Exacerbates Parkinson’s Disease Progression in Male Mice - Xiang Zuo; Hui-Juan Bai; Qi-Li Zhao; Shu-Hui Zhang; Xin Zhao; Xi-Zeng Feng (Molecular Neurobiology, 2025)

Complete genome analysis of a novel nyamivirus from the leaf beetle Aulacophora lewisii - Meng-Nan Chen; Xin-Yi Cai; Zhuang-Xin Ye; Ke-Hui Feng; Peng-Peng Ren; Chuan-Xi Zhang; Jian-Ping Chen; Jun-Min Li; Qianzhuo Mao (Archives of Virology, 2025)

T-2 toxin triggers immunotoxic effects in goats by inducing ferroptosis and neutrophil extracellular traps - Jing Huang; Kaifeng He; Xin Guo; Jiaxuan Wang; Han Hu; Xuhui Zhang; Na Guo; Yiwen Wang; Wenlong Huang; Rongsheng Huang; Tingting Liu; Xi Jiang; et al. (Toxicology and Applied Pharmacology, 2025)

Quantitative in situ Raman monitoring of formation of abundant formate during the hydrogenation of carbon dioxide - Shichuan Xi; Ruifang Huang; Zhendong Luan; Zengfeng Du; Lianfu Li; Guozhi Xie; Weidong Sun; Xin Zhang (Science Bulletin, 2025)

Morphology-dependent performance of Mn doped Co3O4 with preferred exposure of (110) plane for toluene catalytic combustion - Xinxin Wang; Shouxin Xin; Hongyu Yu; Qi Wu; Yanyan Zhang; Haiyang Li; Wei Dai; Xi Chen; Zhongxian Song; Wei Liu; Xuejun Zhang (Journal of Environmental Chemical Engineering, 2025)

Comparative effects of four types of resistant starch on the techno-functional properties of low-fat meat emulsions - Xi-xi Wang; Shuo-meng Li; Jing Wang; Ke-xin Bao; Zhong-kai Zhou (Food Chemistry, 2025)

Toxicity and intergenerational accumulation effect of tire wear particles and their leachate on Brachionus plicatilis - Hairong Lian; Lingyun Zhu; Chunwang Zha; Meng Li; Sen Feng; Fan Gao; Xin Zhang; Yilong Xi; Xinfeng Cheng; Xianling Xiang (Environmental Pollution, 2025)

Polycyclic aromatic hydrocarbons exposure in early pregnancy on child neurodevelopment - Zhi Li; Yu Han; Xinyu Li; Wenjuan Xiong; Tingkai Cui; Wei Xi; Shihao Jin; Xin Zhang (Environmental Pollution, 2025)

A unified low cycle fatigue model of axial-loaded buckling-restrained Fe-SMA plates in high-performance metallic dampers - Xi-Yang Yu; Yan-Wen Li; Junxian Zhao; Xin-Yu Zhao (Engineering Structures, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

The research of nicotinamide and β-arbutin on reducing melanin content in the skin of leopard coral grouper (Plectropomus leopardus) - Zhi Bin Sun; Shi Ying Liu; Xin An Wang; Ai Jun Ma; Zhi Hui Huang; Zhi Feng Liu; Wei Heng Sun; Peng Fei Yan; Dong Hui Gou; Hui Yu Xiao; Hao Zhe Li; Vorathep Muthuwan; et al. (Aquaculture, 2025)

Consuming probiotics protects against cadmium exposure from rice consumption while promotes gut health: An assessment based on a mouse model - Jin-Feng Xi; Lei Zhou; Yao-Sheng Zhang; Xin-Ying Lin; Shan Chen; Rong-Yue Xue; Dongmei Zhou; Hong-Bo Li (Science of The Total Environment, 2025)

Regulating self-assembly of concomitant isotropic Ag78 and anisotropic Ag110 nanoclusters - Xin-Lan Peng; Shuo Huang; Yu-Jing Zhao; Xi-Ming Luo; Hai-Yang Li; Jia-Hua Hu; Jia-Hong Huang; Shuang-Quan Zang (Science Bulletin, 2025)

Benzofurans and dibenzofurans from galls on twigs of the endangered Chinese endemic tree Parrotia subaequalis and their inhibitory properties against Staphylococcus aureus and ATP-citrate lyase - Peng-Jun Zhou; Xi-Ying Wu; Ze-Yu Zhao; Yi Zang; Zhong-Shuai Sun; Yue-Ling Li; Na Li; Juan Xiong; Yeun-Mun Choo; Ze-Xin Jin; Jia Li; Jin-Feng Hu (Phytochemistry, 2025)

A novel approach for predicting adsorbed and free gas content: Insights from adsorbed phase density and volume in supercritical conditions - TengFei Jia; Songhang Zhang; Shuheng Tang; Zhaodong Xi; Di Xin; Qian Zhang; Kaifeng Wang; Ke Zhang; Jianxin Li (Chemical Engineering Journal, 2025)

Mechanism, diffusion, and kinetics characteristics of nitrocellulose denitrification revealed by DFT and MD - Shen Li; Zhong-Xin Liu; Shi-Ying Li; Ya-Jun Ding; Zhong-Liang Xiao; Jie Zhou; Xiao-Qing Wu; Hong-Lei Fan; Zheng-Hong Luo; Xi-Bao Zhang (Chemical Engineering Journal, 2025)

Crosstalk Between the Nervous System and Colorectal Cancer - Xi Li; Chunshui Ye; Min Wang; Patrick Kwan; Xin Tian; Yanke Zhang (Neuroscience Bulletin, 2025)

Development of a machine learning model to support low cost real-time Legionella monitoring in premise plumbing systems - Juan Xu; Xin Li; ChuanWu Xi; Mark H. Weir (Water Research, 2024)

Cadmium bioavailability in market nori and kelp: A comparison with rice and mechanisms underlying reduction in rice cadmium bioavailability with nori and kelp consumption - Xu Duan; Lei Zhou; Sheng-Zhi Chen; Xin-Ying Lin; Rong-Yue Xue; Xi-Mei Xue; Dongmei Zhou; Hong-Bo Li (Science of The Total Environment, 2024)

China-specific unit process dataset for lithium-ion batteries - Xi Tian; Haoyu Li; Fei Peng; Yibing Wang; Kaiwen Xiong; Rongjian Zhao; Min Liao; Yaodan Zhang; Bingqian Zhang; Jinliang Xie; Huimin Chang; Xin Sun; et al. (Resources, Conservation and Recycling, 2024)

Dual-directional regulation of extracellular respiration in Shewanella oneidensis for intelligently treating multi-nuclide contamination - Xin-Lu Cai; Xuan Yao; Li Zhang; Yu-Han Chai; Xuan Liu; Wen-Wen Liu; Ruo-Xi Zhang; Yang-Yang Fan; Xiang Xiao (Journal of Hazardous Materials, 2024)

Response of Potato Growth and Yield to Drought Scenarios Based on APSIM-Potato in the Single-Cropping Region in Northern China - Xin-Lan Luo; Yue Sun; Li-Min Liu; Li-Wei Wang; Xi-Ning Gao (Potato Research, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Accumulation of Prion Triggers the Enhanced Glycolysis via Activation of AMKP Pathway in Prion-Infected Rodent and Cell Models - Qin Fan; Kang Xiao; Ruhan A; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Chao Hu; Xiao-Xi Jia; Chu-Mou Liu; Xin Liu; Cao Chen; Qi Shi; et al. (Molecular Neurobiology, 2024)

Polysaccharides of natural products alleviate antibiotic-associated diarrhea by regulating gut microbiota: a review - Yong Lai; Xin Lan; Yahui Qin; Yuankui Wei; Xi Li; Jianan Feng; Junping Jiang (Archives of Microbiology, 2024)

SIRT5 safeguards against T-2 toxin induced liver injury by repressing iron accumulation, oxidative stress, and the activation of NLRP3 inflammasome - Jing Huang; Yiwen Wang; Han Hu; Kaifeng He; Xi Jiang; Rongsheng Huang; Tingting Liu; Kairao Hu; Xin Guo; Jiaxuan Wang; Dezhi Zhang; Qianyong Li; et al. (Toxicology and Applied Pharmacology, 2024)

A thermoresponsive metabolic nanomodulator for achieving photochemotherapy-sensitized cancer immunotherapy - Shun-Yu Wu; Xiao-Yu Zhu; Xinping Zhang; Yong-Xi Zhou; Shao-Zhe Wang; Yan-Hong Li; Shi-Jie Hao; Tian-Yu Wang; Xin-Wang Yu; Yuxin Guo; Guang-Yu Pan; Bin Xu; et al. (Chemical Engineering Journal, 2024)

The Impact of Bilateral Cerebellar Transcranial Direct Current Stimulation on Balance Control in Healthy Young Adults - Xin Huang; Zhiqin Xu; Lingxiang Zhou; Ke Dong; Qingqing Liu; Jiating Li; Di Lei; Hanjun Liu; Xi Chen (The Cerebellum, 2024)

Eco-friendly and highly efficient PM0.3 air filter made from nonwoven basalt fiber and electrospun nanocellulose fiber - Desalegn Atalie; Ze-Xin Chen; Hui Li; Cun-Guang Liang; Ming-Cheng Gao; Xiao-Xi Cheng; Peng-Cheng Ma (Journal of Hazardous Materials, 2024)

Emerging threat of marine microplastics: Cigarette butt contamination on Yellow Sea beaches and the potential toxicity risks to rotifer growth and reproduction - Hairong Lian; Lingyun Zhu; Meng Li; Sen Feng; Fan Gao; Xin Zhang; Fan Zhang; Yilong Xi; Xianling Xiang (Journal of Hazardous Materials, 2024)

Enhanced in-situ zero-valent iron activated persulfate oxidation with electrokinetics for the remediation of petroleum hydrocarbon contaminated soil - Yong-Tao Li; Qin Sui; Xi Li; Yu-Qin Wang; Xin-Yue Liu; Hao Liu; Wan-Ying Du (Journal of Environmental Chemical Engineering, 2024)

A new strategy for colorimetric detection and removal of butyl xanthate in mineral processing wastewater: Based on a novel nanozyme of Ag@Fe3O4-MnO2 - Kaifeng Duan; Xin Zhao; Xi Chen; Jiangpeng Fu; Qingwei Li; Xiao Zhang; Chuanjun Zheng; Ziming Xin; Zhongtian Fu; Xiaoyu Han; Yang Wang; Cuixia Yang (Journal of Environmental Chemical Engineering, 2024)

A sulfhydryl-functionalized vinylene-linked covalent organic framework for promoting gold recovery by light-assistance - Di Jiang; Zhen-Lei Wang; Yuan-Zhe Cheng; Ya-Xi Yu; Hui-Yuan Kong; Xin-Yue Bian; Xiao-Meng Dou; Shun-Li Li; Dong-Hui Yang; Xuesong Ding; Bao-Hang Han (Chemical Engineering Journal, 2024)

Aerobic Se(IV) reducing bacteria and their reducing characteristics in estuarine sediment - Jiaxing Zhou; Xiangfeng Zeng; Junyi Shi; Sijia Liu; Xiaoming Zhao; Jiaxi Zhang; Weiming Li; Yimei Xi; Shaofeng Wang; Xin Wang; Yongfeng Jia (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Label-free and ultrasensitive detection of environmental lead ions based on spatially localized DNA nanomachines driven by hyperbranched hybridization chain reaction - Xiao-Yu Li; Bo-Xi Zhou; Yu-Ling Xiao; Xin Liu; Yong-Qian Wang; Ming-Min Li; Jun-Ping Wang (Journal of Hazardous Materials, 2024)

Geomechanical perspectives and reviews on the development and evolution of cross-scale discontinuities in the Earth's crust: Patterns, mechanisms and models - Sanbai Li; Zhijiang Kang; Moran Wang; Xi Zhang; Junliang Zhao; Xi-bing Li; Pengzhi Pan; Xin Luo; Hui Wu; Diyuan Li; Fengshou Zhang; Shunda Yuan; et al. (Gas Science and Engineering, 2024)

Construction of large-aperture mesoporous silica spheres supported polyoxometalate heterogeneous catalysts and their high-efficiency for the ultra-deep desulfurization - Jia-Qi Wu; Lu-lu Ma; Zhuang-Zhuang Li; Xin Li; Si-Wen Li; Chang Li; Rong-Xi Li; Jian-She Zhao (Fuel, 2024)

Highly efficient and secure recycling of neomycin fermentation residue by optimum temperature: Nutrients release, neomycin degradation and safety evaluation - Yuefei Li; Jiaqi Hou; Dong Wang; Junhao Ma; Weikai Sun; Mingxiao Li; Zhihao Sun; Yulin Liu; Guocheng Liu; Qinghua Yan; Qianwen Wang; Beidou Xi; et al. (Chemical Engineering Journal, 2024)

Spray of water-in-oil emulsified heavy oil with high water content - Ruo-Fan Shi; Yu-Feng Xi; Li-Tao Wang; Hong-Jun Lu; Xiao Zhang; Xin-Yue Zhang; Zi-Bin Huang; Pei-Qing Yuan (Chemical Engineering Journal, 2024)

Carbon dots with tunable excitation-independent fluorescence and organelle-specific targeting via core graphitization and surface groups engineering - Ming-Yuan Sun; Bao-Hua Tian; Xin-Xin Li; Yu Li; Yu Lei; Xi-Lin Guo; Qiang Miao; Hao Li; Hai-Xia Liang (Chemical Engineering Journal, 2024)

COP-22 Alleviates d-Galactose–Induced Brain Aging by Attenuating Oxidative Stress, Inflammation, and Apoptosis in Mice - Yazhong Ma; Xiaotong Wang; Xin Li; Xi Chen; Zhifeng Teng; Xuekun Wang; Jie Yang; Guoyun Liu (Molecular Neurobiology, 2024)
Aging is a natural and inevitable process of organisms. With the intensification of population aging, research on aging has become a hot topic of global attention. The most obvious manifestation of human aging is the aging of brain function, which has been linked to the development of neurodegenerative diseases. In this study, COP-22, a mono-carbonyl curcumin derivative, was evaluated for its anti-aging ability, especially its ability to resist brain aging induced by D -galactose (D-gal) in mice. For brain protection, COP-22 could resist D-gal–induced oxidative stress by increasing the activity of antioxidative defense enzymes and enhancing antioxidant capacity in the brain tissue; COP-22 could improve the dysfunction of the cholinergic system by decreasing the increased activity of acetylcholinesterase and increasing the reduced content of acetylcholine induced by D-gal; and COP-22 could protect nerve cells of the brain. Further, western blot was used to determine related proteins of the brain. We found that COP-22 could effectively protect against brain injury (SIRT1, p53, p21, and p16) by inhibiting oxidative stress (Nrf2 and HO-1), inflammation (IL-6 and TNF-α), and apoptosis (Bax and caspase-3) in D-gal–induced aging mice. Additionally, COP-22 demonstrated the ability to reduce oxidative stress in serum and liver caused by D-gal, as well as relieve the damages in the liver and kidney induced by D-gal. These results indicated that COP-22 had potential anti-aging activity and could be used in the therapy of aging and aging-associated diseases like Alzheimer disease.

Trees in cooler regions are more vulnerable to thermal stress: Evidence from temperate poplar plantations in Northern China during the 2022 heatwaves - Xin Kong; Shusen Zhang; Aoyu Wang; Yang Liu; Kai Wang; Xiaoning Zhao; Nan Di; Changjun Ding; Ximeng Li; Benye Xi (Agricultural and Forest Meteorology, 2024)

Removal of ciprofloxacin by biosulfurized nano zero-valent iron (BP–S-nZVI) activated peroxomonosulfate: Influencing factors and degradation mechanism - Zheng Peng; Yanni Xi; Zhuang Zhang; Zhu Su; Weihua Xu; Chang Zhang; Xin Li (Chemosphere, 2024)

Tungsten sulfide highly boosted Fe(III)/peroxymonosulfate system for rapid degradation of cyclohexanecarboxylic acid: Performance, mechanisms, and applications - Xin Lv; Dazhen Li; Xi Yu; Kerry N. McPhedran; Rongfu Huang (Chemosphere, 2024)

The complete genome sequence of the planctomycetotal bacterium Bremerella sp. P1 with abundant genes involved in polysaccharide degradation - Jia-Xuan Wang; Jing Wang; Ji-Qing Liu; Jian Li; Wen-Xin Jiang; Fei Xu; Ping-Yi Li; Qi-Long Qin; Xiu-Lan Chen; Xi-Ying Zhang (Marine Genomics, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Surface charge accumulation of functionalized carbonized polymer dots selectively induces lysosomal membrane permeabilization of breast cancer cells - Yu Lei; Bao-Hua Tian; Xin-Xin Li; Ming-Yuan Sun; Xi-Lin Guo; Yi-Da Wang; Hui-Qing Zhou; Ri-Sheng Ma; Hai-Xia Liang (Chemical Engineering Journal, 2024)

CCL2 Potentiates Inflammation Pain and Related Anxiety-Like Behavior Through NMDA Signaling in Anterior Cingulate Cortex - Huan Guo; Wen-chao Hu; Hang Xian; Yun-xin Shi; Yuan-ying Liu; Sui-bin Ma; Kun-qing Pan; Sheng-xi Wu; Li-yan Xu; Ceng Luo; Rou-gang Xie (Molecular Neurobiology, 2024)

Complete genome sequence of a novel amalgavirus in sponge gourd, Luffa cylindrica - Ting Li; Zhuang-Xin Ye; Yao-Liang Huang; Jian-Ping Chen; Chuan-Xi Zhang; Jun-Min Li (Archives of Virology, 2024)

Recovering carbon fibers from waste CFRPs via pyrolysis-oxidation method: Implications for reuse in remanufactured materials - Ming-xin Xu; Xiang-xi Meng; Qi-si Li; Wei-wei Chen; Hong-ji Xue; Hao Jiang; Hai-wen Ji; Qiang Lu (Waste Management, 2024)

Insulin resistance and its relationship with long-term exposure to ozone: Data based on a national population cohort - Zenglei Zhang; Cheng Luan; Chunqi Wang; Tiantian Li; Yi Wu; Xin Huang; Bolin Jin; Enming Zhang; Qiuhong Gong; Xianliang Zhou; Xi Li (Journal of Hazardous Materials, 2024)

Shock tube and modeling study on autoignition properties of ammonia/diethyl ether mixtures at high temperatures - Xin Li; Xianglin Chu; Hua Xiao; Hao Chen; Zhihao Ma; Xin Wang; Shiji Hu; Zhideng Xi (Fuel, 2024)

Water-soluble metal-organic cages crosslinked injectable hydrogel for multi-modal synergistic therapy - Wen-Zhen Li; Xiao-Fan Rong; Yu Wang; Jia-Wen Xiong; Na Zhou; Zi-Xin Wang; Xi-Jia Fang; Wenjing Wang; Yi Liu; Xiao-Qiang Wang (Chemical Engineering Journal, 2024)

How does population outcrossing rate influence seed quality? A case study from a seed tree stand of Pinus massoniana - Wei Wei; Mei-Xi Chen; Xian-Qin Li; Wei-Xin Jiang; Tian-Dao Bai (New Forests, 2024)

Adaptation of a prey population to increasing predation risks - Ling Pan; Han Zhu; Yan Wang; Bao-Chun Shi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen; Yi-Long Xi (Hydrobiologia, 2024)

Complete genome sequence and genetic characterization of a novel segmented RNA virus infecting Nilaparvata lugens - Chao Ning; Zhuang-Xin Ye; Zhong-Tian Xu; Ting Li; Chuan-Xi Zhang; Jian-Ping Chen; Jun-Min Li; Qianzhuo Mao (Archives of Virology, 2024)

Photosynthesis and stress response of coal fly ash on stem elongation in wheat - Shengpu Wang; Xinpeng Hu; Bingbing Li; Haojia Zhang; Xin Xiao; Ruoxi Qian; Xi Huang (Environmental Science and Pollution Research, 2024)

The role of gut microbiota in mediating increased toxicity of nano-sized polystyrene compared to micro-sized polystyrene in mice - Huai Lin; Xin Li; Huihui Gao; Wenjin Hu; Shenbo Yu; Xi Li; Liusheng Lei; Fengxia Yang (Chemosphere, 2024)

Ultrathin (∼30 µm) flexible monolithic perovskite/silicon tandem solar cell - Xinlong Wang; Jingming Zheng; Zhiqin Ying; Xin Li; Meili Zhang; Xuchao Guo; Shiqian Su; Jingsong Sun; Xi Yang; Jichun Ye (Science Bulletin, 2024)

Remediation of petroleum hydrocarbon contaminated soils by nZVI coupled with electrokinetic activation of persulfate - Yong-Tao Li; Yu-Qin Wang; Xi Li; Xin-Yue Liu; Hao Liu; Qin Sui; Wan-Ying Du (Journal of Cleaner Production, 2024)

Application of Dissolved Ozone Flotation in the Advanced Treatment of Drilling Wastewater in Gas Field: Significance of Ozone Microbubble Flocs - Yan Li; Xiao Tong; Jiaxin Xi; Yunhao Li; Xin Guo (Water, Air, & Soil Pollution, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Assessment of heat exposure risk for urban populations and spatio-temporal patterns: A perspective of urban functional zones in Xi'an, China - Xiaojun Huang; Linyu Li; Xi Yan; Wangdi Ji; Kaixu Zhao; Xin Zhao (Urban Climate, 2024)

Turning alkalinity deficiency-induced metabolic disorder into an opportunity for promoting granulation and enhancing heat generation - Xin Li; Xin Wang; Jin-Tao He; Xi Chen; Zhi-Hua Li (Journal of Water Process Engineering, 2024)

Landscape and risk assessment of microplastic contamination in farmed oysters and seawater along the coastline of China - Huai Lin; Xin Li; Wenjin Hu; Shenbo Yu; Xi Li; Liusheng Lei; Fengxia Yang; Yi Luo (Journal of Hazardous Materials, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Methylated derivatives of polycyclic aromatic hydrocarbons in road dust, green belt soil and parking lot dust: occurrence, spatial distribution and emission sources - Jin-Nong Li; Ye Zhang; Jian-Xin Wang; Jie Hu; Xi-Mei Lu; Wen-Xi Xie; Zi-Feng Zhang; Zhong-Hua Tang (Environmental Geochemistry and Health, 2024)

Correction to: BMP2 induces chondrogenic differentiation, osteogenic differentiation and endochondral ossification in stem cells - Nian Zhou; Qi Li; Xin Lin; Ning Hu; Jun-Yi Liao; Liang-Bo Lin; Chen Zhao; Zhen-Ming Hu; Xi Liang; Wei Xu; Hong Chen; Wei Huang (Cell and Tissue Research, 2024)

Molecular detection and genetic characteristics of porcine circovirus 3 and porcine circovirus 4 in central China - Lin-Qing Wang; Jia-Xin Li; Xi-Meng Chen; Xin-Yue Cao; Hong-Lei Zhang; Lan-Lan Zheng; Shi-Jie Ma (Archives of Virology, 2024)

Remediation of diesel contaminated soil by using activated persulfate with Fe3O4 magnetic nanoparticles: effect and mechanisms - Yong-Tao Li; Qin Sui; Xi Li; Xin-Yue Liu; Hao Liu; Yu-Qin Wang; Wan-Ying Du (Environmental Science and Pollution Research, 2024)

Transformation pathways of the carbon-containing group compounds during municipal sludge pyrolysis treatment - Tianxue Yang; Yi Xiao; Xin Zhao; Dongyang Li; Zhifei Ma; Wenxuan Li; Tiancheng Gong; Ting Zhang; Nannan Huang; Beidou Xi. (Waste Management, 2024)

Exposure to haloacetic acid disinfection by-products and male steroid hormones: An epidemiological and in vitro study - Meiping Tian; Huiru Li; Shuangshan Wu; Hanyan Xi; Yi-Xin Wang; Yan-Yang Lu; Liya Wei; Qingyu Huang (Journal of Hazardous Materials, 2024)

Cretaceous integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Dangpeng Xi; Guobiao Li; Shijun Jiang; Xin Rao; Tian Jiang; Tianyang Wang; Zuohuan Qin; Yasu Wang; Jianzhong Jia; Muhammad Kamran; Zhongye Shi; Yuyang Wu; et al. (Science China Earth Sciences, 2024)

Xiashengella succiniciproducens gen. nov., sp. nov., a succinate-producing bacterium isolated from an anaerobic digestion tank in the family Marinilabiliaceae of the order Bacteroidales - Hao-Jie Huang; Xi Zhang; Xin-Wei Sun; Biao Chen; Xiu-Tong Li; Nan Zhou; Rashidin Abdugheni; Qiu-Yin Cheng; Tie-Jun Zhang; Yao Liu; Yong Jiang; Ye Deng; et al. (Archives of Microbiology, 2024)

Panoptic elucidation of algicidal mechanism of Raoultella sp. S1 against the Microcystis aeruginosa by TMT quantitative proteomics - Dongpeng Li; Xi Chen; Yifei Wang; Wei Huang; Yuhui Wang; Xiaoxiang Zhao; Xinshan Song; Xin Cao (Chemosphere, 2024)

Terricoxanthones A–E, unprecedented dihydropyran-containing dimeric xanthones from the endophytic fungus Neurospora terricola HDF-Br-2 associated with the vulnerable conifer Pseudotsuga gaussenii - Hao-Wei Chen; Xi-Ying Wu; Ze-Yu Zhao; Zi-Qi Huang; Xin-Sheng Lei; Guo-Xun Yang; Jiyang Li; Juan Xiong; Jin-Feng Hu (Phytochemistry, 2024)

Fate characteristics and risk quantification of cyflumetofen from tomato cultivation to processing based on large–scale applications - Xi Wang; Li Chen; Xin Ren; Shanshan Kang; Lilin Zhao; Hongxia Zhang; Xianbin Li; Zenglong Chen (Journal of Hazardous Materials, 2024)

Spatial–temporal characteristics and driving factors’ contribution and evolution of agricultural non-CO2 greenhouse gas emissions in China: 1995–2021 - Yuan-yue Chu; Xi-ling Zhang; Yang-chen Guo; Li-juan Tang; Chao-yong Zhong; Ji-wen Zhang; Xin-long Li; De-wen Qiao (Environmental Science and Pollution Research, 2024)

Rapid sand filtration for <10 μm-sized microplastic removal in tap water treatment: Efficiency and adsorption mechanisms - Kassim Chabi; Jianguo Li; Chengsong Ye; Claude Kiki; Xinyan Xiao; Xi Li; Lizheng Guo; Mahmoud Gad; Mingbao Feng; Xin Yu (Science of The Total Environment, 2024)

Associations of remnant cholesterol with cardiovascular and cancer mortality in a nationwide cohort - Yuan Tian; Yi Wu; Minjie Qi; Lijuan Song; Bowang Chen; Chunqi Wang; Jiapeng Lu; Yang Yang; Xiaoyan Zhang; Jianlan Cui; Wei Xu; Hao Yang; et al. (Science Bulletin, 2024)

Retrieving hourly seamless PM2.5 concentration across China with physically informed spatiotemporal connection - Yu Ding; Siwei Li; Jia Xing; Xi Li; Xin Ma; Ge Song; Mengfan Teng; Jie Yang; Jiaxin Dong; Shiyao Meng (Remote Sensing of Environment, 2024)

LncRNA-mir3471-limd1 regulatory network plays critical roles in HIBD - Li Sun; Jun Wan; Bin Sun; Qiuyan Tian; Mei Li; Li-Xiao Xu; Chen-Xi Feng; Xiao Tong; Xing Feng; Xiaofeng Yang; Xin Ding (Experimental Brain Research, 2024)
The purpose of this study was to identify the target genes of tcon_00044595, elucidate its activation site, and provide novel insights into the pathogenesis and treatment of neonatal hypoxic–ischemic brain damage (HIBD). Through homologous blast analysis, we identified predicted target sequences in the neighboring regions of the long non-coding RNA (lncRNA) tcon_00044595, suggesting that limd1 is its target gene. Starbase was utilized to identify potential candidate microRNAs associated with the lncRNA. The interaction between the candidate microRNAs and limd1 was investigated and validated using various experimental methods including in vitro cell culture, cell transfection, dual fluorescence reporter detection system, and real-time PCR. Homology alignment analysis revealed that the lncRNA tcon_00044595 exhibited a 246 bp homologous sequence at the 3' end of the adjacent limd1 gene, with a conservation rate of 68%. Analysis conducted on Starbase online identified three potential microRNA candidates: miR-3471, miR-883a-5p, and miR-214-3p. Intracellular expression of the limd1 gene was significantly down-regulated upon transfection with miR-3471, while the other two microRNAs did not produce noticeable effects. Luciferase reporter assays identified two interaction sites (UTR-1, UTR-2) between miR-3471 and the limd1 3ʹUTR, with UTR-1 exhibiting a strong influence. Further CCK8 assay indicated a protective role of miR-3471 during low oxygen stroke in HIBD. The potential regulatory relationship between lncRNA (tcon_00044595), miR-3471, and the target gene limd1 suggests their involvement in the occurrence and development of HIBD, providing new insights for investigating the underlying mechanisms and exploring targeted therapeutic approaches for HIBD.

Metal(Loid)s in Aquatic Products and Their Potential Health Risk - Shi-Lin Hu; Xiao-Chen Chen; Ying-Xin Xue; Li-Ying Zhi; Yu-Han Yang; Yong-Guan Zhu; Xi-Mei Xue (Exposure and Health, 2024)

Sex-dependent effects of rice cadmium exposure on body weight, gut microflora, and kidney metabolomics based on a mouse model - Jin-Lei Yang; Shan Chen; Jin-Feng Xi; Xin-Ying Lin; Rong-Yue Xue; Lena Q. Ma; Dongmei Zhou; Hong-Bo Li (Science of The Total Environment, 2024)

Sirtuin 3-mediated deacetylation of superoxide dismutase 2 ameliorates sodium fluoride-induced mitochondrial dysfunction in porcine oocytes - Xin-Yue Qi; Jin-Dong Yuan; Zi-Yu Liu; Xi-Qing Jiang; Qi Zhang; Shan-Long Zhang; Lu Zhao; Ling-Yan Ke; Chen-Yuan Zhang; Yan Li; Lu-Yan Zhang; Qian-Qian Xu; et al. (Science of The Total Environment, 2024)

Managing stability of aerobic granules by coordinating diameter and denitrification - Yong-Peng Huang; Xin Wang; Ruo-Lan Wang; Jin-Tao He; Yuan Huang; Zhen-Yu Hang; Xi Chen; Zhi-Hua Li (Science of The Total Environment, 2024)

Natural polymer/wide-bandgap inorganic hybrids for visible-light-driven CO2 photoreduction: Unraveling the multiple effects of interfacial chemical bonding - Jing Li; Yingxi Xiao; Songting Gu; Kejun Wu; Xi Zhao; Xiaoyang Zhao; Junmin Nan; Xin Xiao (Chemical Engineering Journal, 2024)

Fructooligosaccharides and fructans from Platycodon grandiflorum: Structural characterization, lung-oriented guidance and targetability - Jun Liang; Wen-Fei Wang; Yi Zhang; Yan-Qun Chai; Ya-Ge Li; Si-Liang Jiang; Xin-Hua Zhu; Yu-Li Guo; Zhen Wei; Xi-Zhe Sun; Hai-Xue Kuang; Yong-Gang Xia (Carbohydrate Polymers, 2024)

Leg Mechanism Design and Motion Performance Analysis for an Amphibious Crab-like Robot - Shihao Hu; Xinmeng Ma; Xi Chen; Mingfei Xin; Changda Tian; Kaixin Liu; Sicen Li; Liquan Wang; Qinyun Tang; Zhaojin Liu; Mingxuan Ding; Jiawei Li (Journal of Marine Science and Engineering, 2023)
Bionic-legged robots draw inspiration from animal locomotion methods and structures, demonstrating the potential to traverse irregular and unstructured environments. The ability of Portunus trituberculatus (Portunus) to run flexibly and quickly in amphibious environments inspires the design of systems and locomotion methods for amphibious robots. This research describes an amphibious crab-like robot based on Portunus and designs a parallel leg mechanism for the robot based on biological observations. The research creates the group and sequential gait commonly used in multiped robots combined with the form of the robot’s leg mechanism arrangement. This research designed the parallel leg mechanism and modeled its dynamics. Utilizing the outcomes of the dynamics modeling, we calculate the force and torque exerted on each joint of the leg mechanism during group gait and sequential gait when the robot is moving with a load. This analysis aims to assess the performance of the robot’s motion. Finally, a series of performance evaluation experiments are conducted on land and underwater, which show that the amphibious crab-like robot has good walking performance. The crab-like robot can perform forward, backward, left, and right walking well using group and sequential gaits. Simultaneously, the crab-like robot showcases faster movement in group gaits and a more substantial load capacity in sequential gaits.

Study on the performance of Anerinibacillus sp. in degrading cyanide wastewater and its metabolic mechanism - Yao-ting Duan; Wei-da Wang; Si-yuan Qin; Xin Xu; Bo-xi Li; Min-jie Chen; Chun-li Zheng (Chemosphere, 2023)

Diarylpentanoids and phenylpropanoids from the roots of Anthriscus sylvestris (L.) Hoffm - Yan-ling Liu; Yan-gang Cao; Ying Niu; Ya-juan Zheng; Xu Chen; Ying-jie Ren; Xi-ling Fan; Xiang-da Li; Xin-yi Ma; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2023)

A new Trapa from the middle Miocene of Zhangpu, Fujian, southeastern China - Xie-Ting Wu; Zi-Xi Wang; Jun-Wu Shu; Su-Xin Yin; Li-Mi Mao; Gong-Le Shi (Palaeoworld, 2023)

Gas hydrates in shallow sediments as capacitors for cold seep ecosystems: Insights from in-situ experiments - Xiong Zhang; Zhendong Luan; Zengfeng Du; Shichuan Xi; Lianfu Li; Chao Lian; Jianxing Zhang; Ziyu Yin; Liang Ma; Xin Zhang (Earth and Planetary Science Letters, 2023)

Study on Impact Dynamic Behavior and Failure Characteristics of Coal based on True Triaxial Split–Hopkinson Pressure Bar Experiments - Rongxi Shen; Zhoujie Gu; Zhentang Liu; Enlai Zhao; Zesheng Zang; Xin Zhou; Xiaoliang Li; Wei Liu; Xi Wang (Natural Resources Research, 2023)

Strain Rate Effect and Mechanical Constitutive Model of Coal Samples Under Dynamic Load - Zhoujie Gu; Rongxi Shen; Zhentang Liu; Xin Zhou; Xiaoliang Li; Zesheng Zang; Li Zhang; Wei Liu; Xi Wang (Natural Resources Research, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Comparative study about ozonation to treat Microcystis-laden source water at the development and maintenance stage - Xi Li; XuanXuan Xian; Sheng Chen; Weijun Song; Xin Yu; Chang-Ping Yu (Chemosphere, 2023)

An experimental and kinetic modeling study on the ignition characteristics of ammonia/ethanol at high temperatures - Xin Li; Xianglin Chu; Zhihao Ma; Yifan Jin; Xin Wang; Zhideng Xi; Shiji Hu; Hao Chen (Fuel, 2023)

Rapid adaptation of a rotifer prey population to non-consumptive predation pressures - Ling Pan; Han Zhu; Yi-Long Xi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen (Hydrobiologia, 2023)

The modification of meteorological factors on the relationship between air pollution and periodontal diseases: an exploration based on different interaction strategies - Kai Huang; Lin-Fei Feng; Zhe-Ye Liu; Zhen-Hua Li; Yi-Cheng Mao; Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Ying-Qing Li; Jie Wang; Wen-Jie Yu; Xin Cheng; et al. (Environmental Geochemistry and Health, 2023)

Test of the colonization ability of the invasive alien plant Flaveria bidentis (Asteraceae) in southern China - Li Xin-Chen; Chen Xi; Dong Xue-jing; Wang Lai-Le; Yi-chen Li; Shi Zhi-Hua; Song Xiao-ling; Qiang Sheng; Dai Wei-min; Wei-Min Dai (Biological Invasions, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Floating metal phthalocyanine@polyacrylonitrile nanofibers for peroxymonosulfate activation: Synergistic photothermal effects and highly efficient flowing wastewater treatment - Fang Zhang; Jiayu Xin; Xi Wu; Jie Liu; Luyao Niu; Dan Wang; Xinghua Li; Changlu Shao; Xiaowei Li; Yichun Liu (Journal of Hazardous Materials, 2023)

Insights into the pyrolysis mechanisms of epoxy resin polymers based on the combination of experiments and ReaxFF-MD simulation - Ming-xin Xu; Jin-yi Di; Ya-chang Wu; Xiang-xi Meng; Haiwen-Ji; Hao Jiang; Ji-hong Li; Qiang Lu (Chemical Engineering Journal, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Effects of insulin-like growth factor 1, leukemia inhibitory factor, and basic fibroblast growth factor on goat oocyte maturation and early embryonic development in vitro - Zhao Gao-Ping; Shi Pei-Xin; Chang Qing; Wang Zi-Xin; Li Yun-Xia; Zhao Li-Xia; Sun Wei; Wu Meng; Bao Si-Qin; Cao Gui-Fang; Li Xi-He (Small Ruminant Research, 2023)

Molecular mechanism by which StSN2 overexpression inhibits the enzymatic browning of potato - Li-qin Li; Yu-lu Mu; Jing Chen; Qiang Wang; Yi-fei Lu; Sun Xin; Shi-min Yang; Xue-li Huang; Xi-yao Wang; Li-ming Lu (Postharvest Biology and Technology, 2023)

Expression and functional analysis of ace1 and ace2 reveal their differential roles in larval growth and insecticide sensitivity in Spodoptera frugiperda (J. E. Smith, 1797) - Jie Gao; Li-Feng Gong; Huan-Huan Wang; Rui Zhao; Xing Xiao; Xin-Yao Tian; Bo Li; Pei Liang; Xi-Wu Gao; Shao-Hua Gu (Journal of Pest Science, 2023)

Cordythiazole A, the first member of thiazole alkaloids from Chinese cordyceps, with α-glucosidase inhibitory activity - Xue Han; Li-Hua Liu; Xiao-Ying Fang; Shu-Tai Jiang; Huan Zhao; Zheng-Ming Qian; Zhi-Nan Yin; Li-Gong Lu; Chuan-Xi Wang; Xin-Sheng Yao; Hao Gao (Journal of Natural Medicines, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Prolonged fluoride exposure induces spatial-memory deficit and hippocampal dysfunction by inhibiting small heat shock protein 22 in mice - Jinge Xin; Bin Zhu; Hesong Wang; Yong Zhang; Ning Sun; Xi Cao; Liqin Zheng; Yanxi Zhou; Jing Fang; Bo Jing; Kangcheng Pan; Yan Zeng; et al. (Journal of Hazardous Materials, 2023)

Suppression of Microglial ERO1a Alleviates Inflammation and Enhances the Efficacy of Rehabilitative Training After Ischemic Stroke - Jing Ren; Yuan Lv; Qiuyan Tian; Li Sun; Po Miao; Xiaofeng Yang; Li-Xiao Xu; Chen-Xi Feng; Mei Li; Qin Gu; Xing Feng; Xin Ding (Molecular Neurobiology, 2023)

Steam reforming of biomass gasification tar over Ni-based catalyst supported by TiO2-SiO2 composite - Ming-xin Xu; Zi-shu Liu; Xin-yu Zhang; Jin-yi Di; Xiang-xi Meng; Li Zhao; Qiang Lu (Fuel, 2023)

Green waste and sewage sludge feeding ratio alters co-composting performance: Emphasis on the role of bacterial community during humification - Zejin Zhang; Changqun Duan; Yuxian Liu; Anning Li; Xi Hu; Jingkun Chen; Song Zhang; Xin Li; Rongxiao Che; Shiyu Li; Flemming Ekelund; Xiaoyong Cui (Bioresource Technology, 2023)

Numerical study on unsteady propeller exciting characteristics considering shafting whirling vibration effect - Chang-Lin Meng; Zhi-Jun Shuai; Tao Yu; Ke-Xin Ren; Jie Jian; Xi Wang; Dong-Hua Wang; Wan-You Li; Chen-Xing Jiang (Ocean Engineering, 2023)

Crustal thickening and uplift of the northwestern Lhasa Terrane, central Tibetan Plateau: Insights from Mid-Eocene volcanic rocks in the Gerze Region - Xin-Hang Chai; Yun-Chuan Zeng; Ji-Feng Xu; Ming-Jian Li; Feng Huang; Xi-Jun Liu; Qin Chen; Hong-Xia Yu; Shu-Hui Ren (Lithos, 2023)

Effects of Bacillus subtilis BS-Z15 on Intestinal Microbiota Structure and Body Weight Gain in Mice - Jun Yang; Huan-Chen Ning; Qi Zhang; Jun-Qi Yue; Xi-Yuan Cao; Jin-Yu Li; Ling Liu; He-Ping Zhao; Hui-Xin Zhao (Probiotics and Antimicrobial Proteins, 2023)

The Synergistic Activity and Interaction Mechanism of Linoleic Acid and a Bioactive Pentapeptide (Tyr-Val-Pro-His-Trp) from Walnut Meal in the Treatment of Alzheimer’s Disease - Zi-Chun Wang; Yu-Xi Ling; Ya-Xin Liang; Zi-Qi Li; Jie Dai; Di-Feng Ren (International Journal of Peptide Research and Therapeutics, 2023)

Evaluation of storage stability and safety of hypoglycemic Pueraria-Ophiopogon tea - Xin Li; Shuxuan Wang; Mei Chen; Yi Xi; Yuanyuan Shan; Xin Lü (Journal of Stored Products Research, 2023)

Effect of methanol blending on the high-temperature auto-ignition of ammonia: An experimental and modeling study - Xin Li; Zhihao Ma; Yifan Jin; Xin Wang; Zhideng Xi; Shiji Hu; Xianglin Chu (Fuel, 2023)

Cadmium aggravates the blood-brain barrier disruption via inhibition of the Wnt7A/β-catenin signaling axis - Chen-Xi Li; Milton Talukder; Ya-Ru Xu; Shi-Yong Zhu; Ying-Xin Zhao; Jin-Long Li (Environmental Pollution, 2023)

Insight into tetrahydrofuran lignans from Isatis indigotica fortune with neuroprotective and acetylcholinesterase inhibitor activity - Yu-Fei Xi; Ming Bai; Xin Zhang; Zi-Lin Hou; Bin Lin; Guo-Dong Yao; Li-Li Lou; Xiao-Bo Wang; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Potential ecological impacts of physical control on Spartina alterniflora in coastal wetland: Migration and transformation of nutrients and the response of bacterial community structure - Kang Wang; Sen Wang; Xin Zhang; Wenpeng Wang; Fanyi Li; Liu Dong; Fanlong Kong; Min Xi (Journal of Cleaner Production, 2023)

Air pollution in heavy industrial cities along the northern slope of the Tianshan Mountains, Xinjiang: characteristics, meteorological influence, and sources - Yutian Luo; Liping Xu; Zhongqin Li; Xi Zhou; Xin Zhang; Fanglong Wang; Jiajia Peng; Cui Cao; Zhi Chen; Heng Yu (Environmental Science and Pollution Research, 2023)

The development and applications of a controllable lander for in-situ, long-term observation of deep sea chemosynthetic communities - Zengfeng Du; Xiong Zhang; Chao Lian; Zhendong Luan; Shichuan Xi; Lianfu Li; Liang Ma; Jianxing Zhang; Wenzao Zhou; Xiufeng Chen; Zhijun Lu; Chuanbo Wang; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Biotransformation of sulfamonomethoxine in a granular sludge system: Pathways and mechanisms - Meng-Yuan Li; Run-Dong Zhang; Yi-Xing Lin; Qi-Wen Li; Qiu-Yue Zhao; Zong-Xi Zhao; Zhong-Ming Ling; Long-Fei Shu; Min Zhang; Li-Xin Hu; Yi-Jing Shi; Guang-Guo Ying (Chemosphere, 2023)

The conserved L1089 in the S2 subunit of avian infectious bronchitis virus determines viral kidney tropism by disrupting virus-cell fusion - Shu-Yun Li; Yu-Xi Shen; Xue-Lian Xiang; Yong-Xin Li; Nian-Ling Li; An-Dong Wang; Min Cui; Xin-Feng Han; Yong Huang; Jing Xia (Veterinary Microbiology, 2023)

Metagenomics analysis reveals potential pathways and drivers of piglet gut phage-mediated transfer of ARGs - Yalu Ji; Hengyu Xi; Zhen Zhao; Qiujie Jiang; Chong Chen; Xinwu Wang; Fengyang Li; Na Li; Changjiang Sun; Xin Feng; Liancheng Lei; Wenyu Han; et al. (Science of The Total Environment, 2023)

Two new lignans from the herbaceous stems of Ephedra intermedia - Xi-Ling Fan; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Ying-Jie Ren; Xin-Yi Ma; Xiang-Da Li; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Impact of air pollutants on influenza-like illness outpatient visits under urbanization process in the sub-center of Beijing, China - Zhong-Song Zhang; Lu Xi; Li-Li Yang; Xin-Yao Lian; Juan Du; Yan Cui; Hong-Jun Li; Wan-Xue Zhang; Chao Wang; Bei Liu; Yan-Na Yang; Fuqiang Cui; et al. (International Journal of Hygiene and Environmental Health, 2023)

A novel UHPLC-MS/MS method for the determination of four α-dicarbonyl compounds in wine and dynamic monitoring in human urine after drinking - Chao Qi; Yueying Jin; Shengyu Cheng; Lei Di; Xin Wang; Minghui Zhang; Lingli Zhang; Xi-Ling Li; Yu Han; Qingkun Ma; Jun Zhe Min (Food Research International, 2023)

CO2 mineral sequestration and nickel recovery from laterite ore by using waste copperas - Yuxiang Gao; Xi Jin; Liumei Teng; Sohrab Rohani; Minyu He; Jiangling Li; Shan Ren; Qingcai Liu; Junbin Huang; Huamei Duan; Yuntao Xin; Weizao Liu (Fuel, 2023)

Confocal Raman microscopy for assessing effects of preservation methods on symbiotic deep-sea mussel gills - Wanying He; Minxiao Wang; Mengna Li; Zhaoshan Zhong; Hao Chen; Shichuan Xi; Zhendong Luan; Chaolun Li; Xin Zhang (Frontiers in Marine Science, 2022)
Confocal Raman microscopy (CRM) is a powerful tool for biological research, which can provide information regarding the composition and distribution of biomolecules in an in situ, label-free, non-destructive manner and with high spatial resolution. Sample preservation is often an unavoidable step, especially for symbiotic deep-sea samples. Moreover, protocols for the preservation of samples for CRM have not been established and specific effects of different preservation methods on biomolecules have not been studied for relevant samples. In this study, we used deep-sea mussel Gigantidas platifrons , an ideal model in the study of deep-sea symbiosis and investigated the effect of four common preservation methods on the results of CRM imaging and signals. The methods included snap-freeze (SF), SF followed by rapid fixation in methanol (SF-MeOH), 2.5% glutaraldehyde and 2% paraformaldehyde fixation (SF-GP), and 4% paraformaldehyde and alcohol fixation (PS-PA). The results of this study indicate that SF was the most effective method for the comprehensive analysis of the biomolecular composition although the sectioning success rate was relatively low. Moreover, SF-MeOH was found to be effective when SF is not sufficient in obtaining good morphology in sections, or when the effect of chemical bonding on the composition of biomolecules upon SF-MeOH can be neglected. Finally, SF-GP and PS-PA were found to be the most effective methods considering the overall morphological observation. However, they were less suitable for metabolic studies. We believe our results can provide guidance for further studies of Raman on symbiotic deep-sea biological samples. It is of great importance for the wide application of Raman technique.

Ambient fine particulate pollution hysteresis triggers wake-up stroke and rapidly triggers non-wake-up stroke: a case-crossover study - Yan Wang; Yuan Xin; Xi-Xi Wang; Yu-Lei Zhang; Yue Zhang; Yu Wang; Li Peng; Yun-Cheng Wu (Environmental Science and Pollution Research, 2022)

Complete genome analysis of a novel chuvirus from a southern green stink bug (Nezara viridula) - Peng-Peng Ren; Zhuang-Xin Ye; Sai-Nan Wang; Jun-Min Li; Jian-Ping Chen; Chuan-Xi Zhang; Jia-Bao Lu (Archives of Virology, 2022)

Complete genome analysis of a novel iflavirus from the spotted lanternfly Lycorma delicatula - Yi-Zhe Wang; Zhuang-Xin Ye; Jian‑Ping Chen; Chuan‑Xi Zhang; Jun‑Min Li; Hai-Jian Huang (Archives of Virology, 2022)

A Rapid Near-Infrared Fluorescent Probe for Cysteine Based on Isophorone and its Application in B16 Cell Imaging - Yan-Ya Wang; Xue-Shuang Yu; Xin-Jie Li; Hong-Bo Liu; Xi Zhu; Ya-Wen Wang; Yu Peng (Journal of Fluorescence, 2022)

P2X7/P2X4 Receptors Mediate Proliferation and Migration of Retinal Microglia in Experimental Glaucoma in Mice - Meng-Xi Xu; Guo-Li Zhao; Xin Hu; Han Zhou; Shu-Ying Li; Fang Li; Yanying Miao; Bo Lei; Zhongfeng Wang (Neuroscience Bulletin, 2022)

Activation of the TREK-1 Potassium Channel Improved Cognitive Deficits in a Mouse Model of Alzheimer’s Disease by Modulating Glutamate Metabolism - Fang Li; Shu-ning Zhou; Xin Zeng; Zhen Li; Rui Yang; Xue-xi Wang; Bin Meng; Wei-lin Pei; Li Lu (Molecular Neurobiology, 2022)

Correction to: Preliminary analyses of the Tiejiangwan landslide occurred on April 5, 2021 in Hongya County, Sichuan Province, China - Bo Liu; Xiewen Hu; Kun He; Gen Li; Xin Liu; Gang Luo; Chuanjie Xi; Ruichen Zhou (Landslides, 2022)

Preliminary analyses of the Tiejiangwan landslide occurred on April 5, 2021 in Hongya County, Sichuan Province, China - Bo Liu; Xiewen Hu; Kun He; Gen Li; Xin Liu; Gang Luo; Chuanjie Xi; Ruichen Zhou (Landslides, 2022)

Inhibition of visfatin alleviates sepsis-induced intestinal damage by inhibiting Hippo signaling pathway - Zhong-Shen Kuang; Yu-Xin Leng; Ning Yang; Zheng-Qian Li; Ya-Nan Zong; Deng-Yang Han; Yue Li; Jin-Dan He; Xing-Ning Mi; Zhu-Kai Cong; Xi Zhu; Chang-Yi Wu; et al. (Inflammation Research, 2022)
Background The aim of this study is to investigate role of Visfatin, one of the pro-inflammatory adipokines, in sepsis-induced intestinal injury and to clarify the potential mechanism. Methods C57BL/6 mice underwent cecal ligation and puncture (CLP) surgery to establish sepsis model in vivo. Intestinal epithelial cells were stimulated with LPS to mimic sepsis-induced intestinal injury in vitro. FK866 (the inhibitor of Visfatin) with or without XMU-MP-1 (the inhibitor of Hippo signaling) was applied for treatment. The expression levels of Visfatin, NF-κB and Hippo signaling pathways-related proteins were detected by western blot or immunohistochemistry. The intestinal cell apoptosis and intestinal injury were investigated by TUNEL staining and H&E staining, respectively. ELISA was used to determine the production of inflammatory cytokines. Results The expression of Visfatin increased in CLP mice. FK866 reduced intestinal pathological injury, inflammatory cytokines production, and intestinal cell apoptosis in sepsis mice. Meanwhile, FK866 affected NF-κB and Hippo signaling pathways. Additionally, the effects of FK866 on inflammatory response, apoptosis, Hippo signaling and NF-κB signaling were partly abolished by XMU-MP-1, the inhibitor of Hippo signaling. In vitro experiments also revealed that FK866 exhibited a protective role against LPS-induced inflammatory response and apoptosis in intestinal cells, as well as regulating NF-κB and Hippo signaling, whereas addition of XMU-MP-1 weakened the protective effects of FK866. Conclusion In short, this study demonstrated that inhibition of Visfatin might alleviate sepsis-induced intestinal injury through Hippo signaling pathway, supporting a further research on Visfatin as a therapeutic target.

Armochaetoglasins J and K: new cytochalasans from Chaetomium globosum - Li Cheng; Xi Zheng; Qin Li; Meng-Sha Wei; Chun-Mei Chen; Hu-Cheng Zhu; Chang-Li Zeng; Xin-Cai Hao; Yong-Hui Zhang (Natural Product Research, 2022)

PPARγ Dysfunction in the Medial Prefrontal Cortex Mediates High-Fat Diet-Induced Depression - Cong-Cong Fu; Xin-Yi Zhang; Liu Xu; Hui-Xian Huang; Shuang Xu; Qiao-Qi Wu; Zhen Wang; Xi Gu; Li-Fang Lin; Song Lin; Ying-Ying Fang; Xiong Cao; et al. (Molecular Neurobiology, 2022)

Associations between species-level indoor microbiome, environmental characteristics, and asthma in junior high schools of Terengganu, Malaysia - Xi Fu; Yi Meng; Yanling Li; Xunhua Zhu; Qianqian Yuan; Aminnuddin Ma’pol; Jamal Hisham Hashim; Zailina Hashim; Gunilla Wieslander; Yi-Wu Zheng; Xu-Xin Lai; Michael Dho Spangfort; et al. (Air Quality, Atmosphere & Health, 2022)

Two new compounds from a mangrove sediment-derived fungus Penicillium polonicum H175 - Shun-Zhi Liu; Xi-Xiang Tang; Feng-Ming He; Jian-Xin Jia; Hang Hu; Bao-Ying Xie; Ming-Yu Li; Ying-Kun Qiu (Natural Product Research, 2022)

Differences of carbon and nitrogen stoichiometry between different habitats in two natural Korean pine forests in Northeast China’s mountainous areas - Ya-fei Wang; Wen-biao Duan; Mei-xue Qu; Li-xin Chen; Hang-yu Lan; Xi-feng Yang; Si-jing Meng; Jia Chen (Journal of Mountain Science, 2022)

The Oxidative Damage and Morphological Changes of Sugar Beet (Beta vulgaris L.) Leaves at Seedlings Stage Exposed to Boron Deficiency in Hydroponics - Xin Song; Xueming Hao; Baiquan Song; Xiaoyu Zhao; Zhenzhen Wu; Xiangling Wang; Jiyu Du; Wengong Huang; Muhammad Riaz; Xingfan Li; Jiaxin Li; Meiyu Li; et al. (Sugar Tech, 2022)

Alternaria species causing leaf spot on hemp (Cannabis sativa) in Northern China - Hong Cheng; Lin Zhao; Xin Wei; Xi Liu; Guo-Yang Gao; Jian-Xin Deng; Mei-Jia Li (European Journal of Plant Pathology, 2022)

Haloprofundus salilacus sp. nov., Haloprofundus halobius sp. nov. and Haloprofundus salinisoli sp. nov.: three extremely halophilic archaea isolated from salt lake and saline soil - Si-Ya Li; Yu-Jie Xin; Chen-Xi Bao; Jing Hou; Heng-Lin Cui (Extremophiles, 2022)

Complete genome analysis of a novel picorna-like virus from a ladybird beetle (Cheilomenes sexmaculata) - Yu-Juan He; Zhuang-Xin Ye; Jian-Ping Chen; Chuan-Xi Zhang; Gang Lu; Jun-Min Li (Archives of Virology, 2022)

Complete genome sequence of a novel arlivirus from a yellow spotted stink bug (Erthesina fullo (Thunberg, 1783)) - Zhuang-Xin Ye; Shao-Min Wang; Gang Lu; Jian-Ping Chen; Chuan-Xi Zhang; Liao-Yuan Xu; Jun-Min Li (Archives of Virology, 2022)

Seasonal variations of rotifer communities in three climatic zones: effects of environmental parameters on changes of functional groups - Fang-Ping Qian; Xin-Li Wen; Yi-Long Xi (Limnology, 2022)

Complete genome analysis of a nege-like virus in aphids (Astegopteryx formosana) - Xiao-Di Zhang; Gang Lu; Zhuang-Xin Ye; Jian-Ping Chen; Chuan-Xi Zhang; Jun-Min Li (Archives of Virology, 2022)

The first description of alate and supplementary description of soldier of Reticulitermes aculabialis Tsai et Hwang (Isoptera, Rhinotermitidae) - Zahid Khan; Yu-Xin Li; Qing Liu; Xiao-Hong Su; Lian-Xi Xing (International Journal of Tropical Insect Science, 2021)

Three-dimensional reconstruction of pore canals in the cuticle of the brown planthopper - Dan-Ting Li; Jian-Sheng Guo; Xin-Qiu Wang; Bernard Moussian; Chuan-Xi Zhang (Science China Life Sciences, 2021)

The intellectual capital efficiency and corporate sustainable growth nexus: comparison from agriculture, tourism and renewable energy sector - Xin Long Xu; Jianping Li; Dengsheng Wu; Xi Zhang (Environment, Development and Sustainability, 2021)

Novel Alcaligenes ammonioxydans sp. nov. from wastewater treatment sludge oxidizes ammonia to N 2 with a previously unknown pathway - Meng‐Ru Wu; Ting‐Ting Hou; Ying Liu; Li‐Li Miao; Guo‐Min Ai; Lan Ma; Hai‐Zhen Zhu; Ya‐Xin Zhu; Xi‐Yan Gao; Craig W. Herbold; Michael Wagner; De‐Feng Li; et al. (Environmental Microbiology, 2021)
Summary Heterotrophic nitrifiers are able to oxidize and remove ammonia from nitrogen‐rich wastewaters but the genetic elements of heterotrophic ammonia oxidation are poorly understood. Here, we isolated and identified a novel heterotrophic nitrifier, Alcaligenes ammonioxydans sp. nov. strain HO‐1, oxidizing ammonia to hydroxylamine and ending in the production of N 2 gas. Genome analysis revealed that strain HO‐1 encoded a complete denitrification pathway but lacks any genes coding for homologous to known ammonia monooxygenases or hydroxylamine oxidoreductases. Our results demonstrated strain HO‐1 denitrified nitrite (not nitrate) to N 2 and N 2 O at anaerobic and aerobic conditions respectively. Further experiments demonstrated that inhibition of aerobic denitrification did not stop ammonia oxidation and N 2 production. A gene cluster ( dnfT1RT2ABCD ) was cloned from strain HO‐1 and enabled E . coli accumulated hydroxylamine. Sub‐cloning showed that genetic cluster dnfAB or dnfABC already enabled E . coli cells to produce hydroxylamine and further to 15 N 2 from ( 15 NH 4 ) 2 SO 4 . Transcriptome analysis revealed these three genes dnfA , dnfB and dnfC were significantly upregulated in response to ammonia stimulation. Taken together, we concluded that strain HO‐1 has a novel dnf genetic cluster for ammonia oxidation and this dnf genetic cluster encoded a previously unknown pathway of di rect amm onia ox idation (Dirammox) to N 2 .

Transcriptome profiling reveals key genes in regulation of the tepal trichome development in Lilium pumilum D.C. - Yin Xin; Wenqiang Pan; Xi Chen; Yixin Liu; Mingfang Zhang; Xuqing Chen; Fengping Yang; Jingru Li; Jian Wu; Yunpeng Du; Xiuhai Zhang (Plant Cell Reports, 2021)

Two Foxo1 homologues in the orange-spotted grouper Epinephelus coioides: sequences, expression, and possible involvement in the activation of cyp19a1a expression in the ovary - Yunfeng Ning; Miao Fan; Qiongyou Liu; Huijie Lu; Shangyong Qian; Xin Cui; Feiyan Meng; Xi Li; Xing Xu; Shu Sun; Youwei Zhang; Lihong Zhang; et al. (Fish Physiology and Biochemistry, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

The association between hand grip strenght and global PSQI score in the middleaged and elderly population - Jinlin Li; Qingping Zhang; Qi Wang; Lingli Zhou; Xin Wan; Xi Zeng (Sleep and Biological Rhythms, 2021)

Multi-decadal trends in the tropical Pacific western boundary currents retrieved from historical hydrological observations - Shijian Hu; Xi Lu; Shihan Li; Fan Wang; Cong Guan; Dunxin Hu; Linchao Xin; Jie Ma (Science China Earth Sciences, 2021)
As large-scale ocean circulation is a key regulator in the redistribution of oceanic energy, evaluating the multi-decadal trends in the western Pacific Ocean circulation under global warming is essential for not only understanding the basic physical processes but also predicting future climate change in the western Pacific. Employing the hydrological observations of World Ocean Atlas 2018 (WOA18) from 1955 to 2017, this study calculated the geostrophic currents, volume transport and multi-decadal trends for the North Equatorial Current (NEC), the North Equatorial Countercurrent (NECC), the Mindanao Current (MC), the Kuroshio Current (KC) in the origin and the New Guinea Coastal Undercurrent (NGCUC) within tropical western Pacific Ocean over multi-decades. Furthermore, this study examined the contributions of temperature and salinity variations. The results showed significant strengthening trends in NEC, MC and NGCUC over the past six decades, which is mainly contributed by temperature variations and consistent with the tendency in the dynamic height pattern. Zonal wind stress averaged over the western Pacific Ocean in the same latitude of each current represents the decadal variation and multi-decadal trends in corresponding ocean currents, indicating that the trade wind forcing plays an important role in the decadal trend in the tropical western Pacific circulation. Uncertainties in the observed hydrological data and trends in the currents over the tropical western Pacific are also discussed. Given that the WOA18 dataset covers most of the historical hydrological sampling data for the tropical western Pacific, this paper provides important observational information on the multi-decadal trend of the large-scale ocean circulation in the western Pacific.

Postsynaptic Targeting and Mobility of Membrane Surface-Localized hASIC1a - Xing-Lei Song; Di-Shi Liu; Min Qiang; Qian Li; Ming-Gang Liu; Wei-Guang Li; Xin Qi; Nan-Jie Xu; Guang Yang; Michael Xi Zhu; Tian-Le Xu (Neuroscience Bulletin, 2021)
Acid-sensing ion channels (ASICs), the main H + receptors in the central nervous system, sense extracellular pH fluctuations and mediate cation influx. ASIC1a, the major subunit responsible for acid-activated current, is widely expressed in brain neurons, where it plays pivotal roles in diverse functions including synaptic transmission and plasticity. However, the underlying molecular mechanisms for these functions remain mysterious. Using extracellular epitope tagging and a novel antibody recognizing the hASIC1a ectodomain, we examined the membrane targeting and dynamic trafficking of hASIC1a in cultured cortical neurons. Surface hASIC1a was distributed throughout somata and dendrites, clustered in spine heads, and co-localized with postsynaptic markers. By extracellular pHluorin tagging and fluorescence recovery after photobleaching, we detected movement of hASIC1a in synaptic spine heads. Single-particle tracking along with use of the anti-hASIC1a ectodomain antibody revealed long-distance migration and local movement of surface hASIC1a puncta on dendrites. Importantly, enhancing synaptic activity with brain-derived neurotrophic factor accelerated the trafficking and lateral mobility of hASIC1a. With this newly-developed toolbox, our data demonstrate the synaptic location and high dynamics of functionally-relevant hASIC1a on the surface of excitatory synapses, supporting its involvement in synaptic functions.

Altered resting-state networks may explain the executive impairment in young health immigrants into high-altitude area - Xiaoming Chen; Jian Liu; Jiye Wang; Zhenlong Xin; Qian Zhang; Wenbin Zhang; Yibin Xi; Yuanqiang Zhu; Chen Li; Jiaming Li; Yuedong Han; Jie Liu; et al. (Brain Imaging and Behavior, 2021)

Complete genome analysis of a novel iflavirus from a leaf beetle, Aulacophora lewisii - Zhuang-Xin Ye; Yue-Hong Li; Jian-Ping Chen; Chuan-Xi Zhang; Jun-Min Li (Archives of Virology, 2021)

Patterns of intrinsic brain activity in essential tremor with resting tremor and tremor-dominant Parkinson’s disease - Jun-ying Li; Zhong-jiao Lu; Xue-ling Suo; Nan-nan Li; Du Lei; Ling Wang; Jia-xin Peng; Li-ren Duan; Jing Xi; Yi Jiang; Qi-yong Gong; Rong Peng (Brain Imaging and Behavior, 2020)

Correction to: Genome-wide characterization of the cellulose synthase gene superfamily in Pyrus bretschneideri and reveal its potential role in stone cell formation - Guohui Li; Xin Liu; Yuxuan Liang; Yang Zhang; Xi Cheng; Yongping Cai (Functional & Integrative Genomics, 2020)

LncRNA NFIA-AS2 promotes glioma progression through modulating the miR-655-3p/ZFX axis - Jun Xin; Yu-Hong Zhao; Xi-Yun Zhang; Li-Qiang Tian (Human Cell, 2020)

Application of confocal laser Raman spectroscopy on marine sediment microplastics - Jing Liu; Xin Zhang; Zengfeng Du; Zhendong Luan; Lianfu Li; Shichuan Xi; Bing Wang; Lei Cao; Jun Yan (Journal of Oceanology and Limnology, 2020)

Genome-wide characterization of the cellulose synthase gene superfamily in Pyrus bretschneideri and reveal its potential role in stone cell formation - Guohui Li; Xin Liu; Yuxuan Liang; Yang Zhang; Xi Cheng; Yongping Cai (Functional & Integrative Genomics, 2020)

The Intruding Wolbachia Strain from the Moth Fails to Establish Itself in the Fruit Fly Due to Immune and Exclusion Reactions - Xin-Chao Liu; Yue-Ru Li; Bei Dong; Zheng-Xi Li (Current Microbiology, 2020)

Simultaneous calcium recordings of hippocampal CA1 and primary motor cortex M1 and their relations to behavioral activities in freely moving epileptic mice - Xi Dong; Xin Zhang; Feifei Wang; Nannan Liu; Aili Liu; Yuanyuan Li; Liangpeng Wei; Feng Chen; Shiyang Yuan; Kai Zhang; Shaowei Hou; Qingyan Jiao; et al. (Experimental Brain Research, 2020)

Preparation of non-sintered lightweight aggregates through co-mechanochemical treatment of oil-contaminated drill cuttings, circulation fluidized bed combustion fly ash, and quicklime - Xiaoyue Chen; Zhonghui Xu; Zhengzhen Yao; Qin Shuai; Zao Jiang; Xi Peng; Yu Li; Ran An; Xin Jiang; Han Li (Environmental Science and Pollution Research, 2020)

A survey of microbial contamination in aviation fuel from aircraft fuel tanks - Dong Hu; Jie Zeng; Shangshu Wu; Xi Li; Chengsong Ye; Wenfang Lin; Xin Yu (Folia Microbiologica, 2020)

The Jasmonic Acid Pathway Positively Regulates the Polyphenol Oxidase-Based Defense against Tea Geometrid Caterpillars in the Tea Plant (Camellia sinensis) - Jin Zhang; Xin Zhang; Meng Ye; Xi-Wang Li; Song-Bo Lin; Xiao-Ling Sun (Journal of Chemical Ecology, 2020)

Three-dimensional architecture of a mechanoreceptor in the brown planthopper, Nilaparvata lugens, revealed by FIB-SEM - Jian-Sheng Guo; Xin-Qiu Wang; Dan-Ting Li; Dan-Dan Song; Chuan-Xi Zhang (Cell and Tissue Research, 2020)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

FAR gene enables the brown planthopper to walk and jump on water in paddy field - Dan-Ting Li; Xuan Chen; Xin-Qiu Wang; Chuan-Xi Zhang (Science China Life Sciences, 2019)

Rapid adaptation of Brachionus angularis (Rotifera) to invasion by Brachionus calyciflorus - Yi-Long Xi; Ke-Qiang Huang; Ling Pan; Han Zhu; Ya-Li Ge; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2019)

Experimental Research on the Impact of Alveolar Morphology on Deposition of Inhalable Particles in the Human Pulmonary Acinar Area - Rong Li; Xin-Xi Xu; Yang Qiao; Xiu-Guo Zhao (Journal of Medical and Biological Engineering, 2019)

Spatial distribution patterns of rock fragments and their underlying mechanism of migration on steep hillslopes in a karst region of Yunnan Province, China - Juan Liu; You-xin Shen; Xi-ai Zhu; Gao-juan Zhao; Zhi-meng Zhao; Zhen-jiang Li (Environmental Science and Pollution Research, 2019)

U13 → C13 mutation in the variable region of the NA gene 3′UTR of H9N2 influenza virus influences the replication and transcription of NA and enhances virus infectivity - Xi Li; Yanci Chen; Xin Wang; Bo Peng; Weihua Wu; Hui Liu; Ying Sun; Xiujuan Tang; Qing Zheng; Shisong Fang (Virus Genes, 2019)

Mesorhizobium carbonis sp. nov., isolated from coal bed water - Jing Li; Wen Xin; Zhen-Zhen Xu; Fang-Qin Xiang; Jing-Jing Zhang; Li-Jun Xi; Jian-Bo Qu; Jian-Guo Liu (Antonie van Leeuwenhoek, 2019)

Disruption of a Upf1-like helicase-encoding gene OsPLS2 triggers light-dependent premature leaf senescence in rice - Pan Gong; Yanmin Luo; Fudeng Huang; Yaodong Chen; Chaoyue Zhao; Xin Wu; Kunyu Li; Xi Yang; Fangmin Cheng; Xun Xiang; Chunyan Wu; Gang Pan (Plant Molecular Biology, 2019)

Influences of soil moisture and salt content on loess shear strength in the Xining Basin, northeastern Qinghai-Tibet Plateau - Jiang-tao Fu; Xia-song Hu; Xi-lai Li; Dong-mei Yu; Ya-bin Liu; You-Qing Yang; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2019)

Diffuse Intrinsic Pontine Gliomas Exhibit Cell Biological and Molecular Signatures of Fetal Hindbrain-Derived Neural Progenitor Cells - Yu Sun; Cheng Xu; Changcun Pan; Xin Chen; Yibo Geng; Yuliang Wu; Peng Zhang; Wenhao Wu; Yu Wang; Deling Li; Zhen Wu; Junting Zhang; et al. (Neuroscience Bulletin, 2019)

Population pharmacokinetics of oxcarbazepine active metabolite in Chinese paediatric epilepsy patients and its application in individualised dosage regimens - Wei-wei Lin; Xi-wen Li; Zheng Jiao; Jin Zhang; Xin Rao; Da-yong Zeng; Xin-hua Lin; Chang-lian Wang (European Journal of Clinical Pharmacology, 2019)

Programmed cell death induced by cadmium stress and/or boron deprivation in tobacco (Nicotiana tabacum L.) cultivar Bright Yellow 2 cells - Li Ping Jiang; Lin Zi; Xiao Fang Liu; Zi-Xi Liu; Lai Fu Zhong; Xiang Xin Xue (In Vitro Cellular & Developmental Biology - Plant, 2019)

Screening and Mutation of Saccharomyces cerevisiae UV-20 with a High Yield of Second Generation Bioethanol and High Tolerance of Temperature, Glucose and Ethanol - Shi Yi; Xiao Zhang; Han-xin Li; Xiao-xia Du; Shao-wei Liang; Xi-hua Zhao (Indian Journal of Microbiology, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Altered Profiles of Gut Microbiota in Klebsiella pneumoniae-Induced Pyogenic Liver Abscess - Nan Chen; Zong-Xin Ling; Tong-Tong Jin; Ming Li; Sheng Zhao; Li-Shuang Zheng; Xin Xi; Lin-Lin Wang; Ying-Ying Chen; Yue-Liang Shen; Li-Ping Zhang; Shao-cong Sun (Current Microbiology, 2018)

Variable hydrological effects of herbs and shrubs in the arid northeastern Qinghai-Tibet Plateau, China - Ya-bin Liu; Ying Zhang; Jiang-tao Fu; Dong-mei Yu; Xia-song Hu; Xi-lai Li; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2018)

Comprehensive bioinformation analysis of the miRNA of PLCE1 knockdown in esophageal squamous cell carcinoma - Xiaobin Cui; Kaige Wang; Xinqian Yang; Hao Peng; Xi Chen; Huahua Xin; Yanxia Tian; Yunzhao Chen; Feng Li (Molecular and Cellular Biochemistry, 2018)

Particulate and gaseous pollutants in a petrochemical industrialized valley city, Western China during 2013–2016 - Xi Zhou; Tingjun Zhang; Zhongqin Li; Yan Tao; Feiteng Wang; Xin Zhang; Chunhai Xu; Shan Ma; Ju Huang (Environmental Science and Pollution Research, 2018)

Insights into the redox components of dissolved organic matters during stabilization process - Ying Yuan; Bei-Dou Xi; Xiao-Song He; Yan Ma; Hui Zhang; Dan Li; Xin-Yu Zhao (Environmental Science and Pollution Research, 2018)

Ursolic acid, a potential anticancer compound for breast cancer therapy - Ran Yin; Tong Li; Jing Xin Tian; Pan Xi; Rui Hai Liu (Critical Reviews in Food Science and Nutrition, 2018)

Sumoylation of SUVR2 contributes to its role in transcriptional gene silencing - Yu-Xi Luo; Yong-Feng Han; Qiu-Yuan Zhao; Jin-Lu Du; Kun Dou; Lin Li; She Chen; Xin-Jian He (Science China Life Sciences, 2018)

Temporal patterns and processes of genetic differentiation of the Brachionus calyciflorus (Rotifera) complex in a subtropical shallow lake - Ye Zhang; Ao Zhou; Yi-Long Xi; Qiang Sun; Le-Feng Ning; Ping Xie; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Progesterone levels in seasonally breeding, free-ranging male Macaca thibetana - Dong-Po Xia; Xi Wang; Qi-Xin Zhang; Bing-Hua Sun; Lixing Sun; Lori K. Sheeran; Jin-Hua Li (Mammal Research, 2018)

Endosymbiont CLS-HI plays a role in reproduction and development of Haemaphysalis longicornis - Chun-Mian Zhang; Ning-Xin Li; Tian-Tian Zhang; Zhao-Xi Qiu; Yuan Li; Li-Wu Li; Jing-Ze Liu (Experimental and Applied Acarology, 2017)

Two new cadinane-type sesquiterpenes from cultures of the basidiomycete Trichaptum pargamenum - Bin Tang; Xi Du; Han-An Long; Jun Du; Jian-Min Guo; Xin Hu; Hua Tu; Li Yang; Hong-Jin Liu (Natural Product Research, 2017)

Combined Effects of Temperature and the Microcystin MC-LR on the Feeding Behavior of the Rotifer Brachionus calyciflorus - Xian-Ling Xiang; Ying-Ying Chen; Qiu-Lei Xu; Ling-Yun Zhu; Xin-Li Wen; Yi-Long Xi (Bulletin of Environmental Contamination and Toxicology, 2017)

Long-Term Generation Scheduling of Hydropower System Using Multi-Core Parallelization of Particle Swarm Optimization - Sheng-li Liao; Ben-xi Liu; Chun-tian Cheng; Zhi-fu Li; Xin-yu Wu (Water Resources Management, 2017)

A new tetrahydrobenzofuranone metabolite from Streptomyces sp. HS-NF-853 - Kai Yan; Jin-Meng Li; Ren-Xin Xiang; Jian-Song Li; Hui Zhang; Huan Qi; Chong-Xi Liu; Ji-Dong Wang; Wen-Sheng Xiang (Natural Product Research, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

RNAi as a tool to control the sex ratio of mouse offspring by interrupting Zfx/Zfy genes in the testis - YongSheng Zhang; JiFeng Xi; Bin Jia; XiangZu Wang; XuHai Wang; ChaoCheng Li; YaQiang Li; XianCun Zeng; RuiWen Ying; Xin li; Song Jiang; FangYuan Yuan (Mammalian Genome, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

A new macrolactin antibiotic from deep sea-derived bacteria Bacillus subtilis B5 - Wei Li; Xi-Xiang Tang; Xia Yan; Zhen Wu; Zhi-Wei Yi; Mei-Juan Fang; Xin Su; Ying-Kun Qiu (Natural Product Research, 2016)

Copper chelation by trientine dihydrochloride inhibits liver RFA-induced inflammatory responses in vivo - Ji-ming Yin; Li-bo Sun; Jia-sheng Zheng; Xin-xin Wang; De-xi Chen; Ning Li (Inflammation Research, 2016)

BMP2 induces chondrogenic differentiation, osteogenic differentiation and endochondral ossification in stem cells - Nian Zhou; Qi Li; Xin Lin; Ning Hu; Jun-Yi Liao; Liang-Bo Lin; Chen Zhao; Zhen-Ming Hu; Xi Liang; Wei Xu; Hong Chen; Wei Huang (Cell and Tissue Research, 2016)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

A sensitive immunochromatographic assay using colloidal gold–antibody probe for rapid detection of fumonisin B 1 in corn - Xi-Chun Wang; Hai-Xin Fan; Meng-Xue Fan; Fu-Hui Li; Shi-Bin Feng; Jin-Chun Li; Jin-Jie Wu; Yu Li; Jia-Sheng Wang (Food Additives & Contaminants: Part A, 2016)

150 Million year history of North China Craton disruption preserved in Mesozoic sediments of the Ordos basin - Zhen-Hong Li; Sheng-Li Xi; Sheng-Bin Feng; Xin-She Liu (International Geology Review, 2016)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Genome-wide Screening of Human Papillomavirus-Specific CTL Epitopes Presented by HLA-A Alleles in Cervical Cancer - Qiao-Hong Wang; Xiang-Yang Gao; Xue-Ling Lou; Li Yao; Zhan-Xin Zhang; Xi-Hong Zhang; Yu-Hong Xia; Bei-Bei Liu; Li-Li Zhang (International Journal of Peptide Research and Therapeutics, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Association between occupational stressors and type 2 diabetes among Chinese police officers: a 4-year follow-up study in Tianjin, China - Hao Yu; Jin-chuan Liu; Ya-jiao Fan; Chen Li; Li-xin Zhang; Xi Chen; Song Yue; Wen-li Lu; Xi-lin Yang; Nai-jun Tang (International Archives of Occupational and Environmental Health, 2016)

Association of Alpha-Soluble NSF Attachment Protein with Epileptic Seizure - Zhiqin Xi; Wanni Deng; Liang Wang; Fei Xiao; Jie Li; Zhihua Wang; Xin Wang; Xiujuan Mi; Na Wang; Xuefeng Wang (Journal of Molecular Neuroscience, 2015)

Transarterial Onyx Embolization for Patients with Cavernous Sinus Dural Arteriovenous Fistulas Who Have Failed Transvenous Embolization - Jun Wen; Chuan-Zhi Duan; Li-Jing Huang; Xin Zhang; Xu-Ying He; Xi-Feng Li (Cell Biochemistry and Biophysics, 2015)

Enzymatic synthesis of aroma acetoin fatty acid esters by immobilized Candida antarctica lipase B - Zijun Xiao; Xiaoyuan Hou; Xin Lyu; Jing-yi Zhao; Lijun Xi; Jing Li; Jian R. Lu (Biotechnology Letters, 2015)

Identification of Mycobacterium tuberculosis PPE68-Specific HLA-A*0201-Restricted Epitopes for Tuberculosis Diagnosis - Zhi-liang Duan; Qiang Li; Sina Wang; Xin-yu Chen; Hui-fang Liu; Bo-kun Chen; De-zhou Li; Xi Huang; Jin-sheng Wen (Current Microbiology, 2015)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Identifying and Characterizing Resting State Networks in Temporally Dynamic Functional Connectomes - Xin Zhang; Xiang Li; Changfeng Jin; Hanbo Chen; Kaiming Li; Dajiang Zhu; Xi Jiang; Tuo Zhang; Jinglei Lv; Xintao Hu; Junwei Han; Qun Zhao; et al. (Brain Topography, 2014)

Beta Amyloid Peptide (25-35) Leading to Inflammation Through Toll-Like Receptors and the Anti-inflammatory Effect of Genistein in BV-2 Cells - Huan-Ling Yu; Xiao-Ying Li; Xin Zhou; Lin-Hong Yuan; Wei-Wei Ma; Yuan-Di Xi; Xia Zhao; Jian Wu; Rong Xiao (Journal of Molecular Neuroscience, 2013)

Prolonged environmental exposure of arsenic through drinking water on the risk of hypertension and type 2 diabetes - Xin Li; Bing Li; Shuhua Xi; Quanmei Zheng; Xiuqiang Lv; Guifan Sun (Environmental Science and Pollution Research, 2013)

Genetic and epigenetic differentiation between natural Betula ermanii (Betulaceae) populations inhabiting contrasting habitats - Wei-Qing Wu; Ma Re Yi; Xin-Feng Wang; Li-Li Ma; Lily Jiang; Xi-Wen Li; Hong-Xing Xiao; Ming-Zhou Sun; Lin-Feng Li; Bao Liu (Tree Genetics & Genomes, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Association of PON1 genotype and haplotype with susceptibility to coronary artery disease and clinical outcomes in dual antiplatelet-treated Han Chinese patients - Yan-Hong Kang; Hai-Yan Lao; Hong Wu; Wei-Hua Lai; Xin-Xin Li; Xi-Yong Yu; Ji-Yan Chen; Shi-Long Zhong (European Journal of Clinical Pharmacology, 2013)

Studies on Antibacterial Mechanisms of Copper Complexes with 1,10-phenanthroline and Amino Acid on Escherichia coli - Xin Liu; Xi Li; Zhijun Zhang; Yulin Dong; Peng Liu; Chaocan Zhang (Biological Trace Element Research, 2013)

Effect of Coriolus versicolor polysaccharides on the hematological and biochemical parameters and protection against Aeromonas hydrophila in allogynogenetic crucian carp (Carassius auratus gibelio) - Zhi-xin Wu; Su-feng Pang; Xiao-xuan Chen; Yan-mei Yu; Jin-min Zhou; Xi Chen; Li-jiao Pang (Fish Physiology and Biochemistry, 2013)

A non-synonymous SNP in the NOS2 associated with septic shock in patients with sepsis in Chinese populations - Zhifu Wang; Kai Feng; Maoxing Yue; Xiaoguang Lu; Qihan Zheng; Hongxing Zhang; Yun Zhai; Peiyao Li; Lixia Yu; Mi Cai; Xiumei Zhang; Xin Kang; et al. (Human Genetics, 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

Wnt/β-catenin signaling induces the aging of mesenchymal stem cells through promoting the ROS production - Da-yong Zhang; Yu Pan; Chong Zhang; Bing-xi Yan; Shan-shan Yu; Dong-ling Wu; Meng-meng Shi; Kai Shi; Xin-xiao Cai; Shuang-shuang Zhou; Jun-bo Wang; Jian-ping Pan; et al. (Molecular and Cellular Biochemistry, 2013)

Autophagy appears during the development of the mouse lower first molar - Jing-wen Yang; Ling-xin Zhu; Guo-hua Yuan; Yang-xi Chen; Li Zhang; Lu Zhang; Zhi Chen (Histochemistry and Cell Biology, 2013)

Cloning arginine kinase gene and its RNAi in Bursaphelenchus xylophilus causing pine wilt disease - Xin-rong Wang; Xi Cheng; Ya-dong Li; Jin-ai Zhang; Zhi-fen Zhang; Han-rong Wu (European Journal of Plant Pathology, 2012)

High levels of glucose induce “metabolic memory” in cardiomyocyte via epigenetic histone H3 lysine 9 methylation - Xi-Yong Yu; Yong-Jian Geng; Jia-Liang Liang; Saidan Zhang; He-Ping Lei; Shi-Long Zhong; Qiu-Xiong Lin; Zhi-Xin Shan; Shu-Guang Lin; Yangxin Li (Molecular Biology Reports, 2012)

Involvement of p38MAPK/NF-κB Signaling Pathways in Osteoblasts Differentiation in Response to Mechanical Stretch - Liang Wang; Jian-yu Li; Xi-zheng Zhang; Lu Liu; Zong-ming Wan; Rui-xin Li; Yong Guo (Annals of Biomedical Engineering, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Hydrogen sulfide protects H9c2 cells against doxorubicin-induced cardiotoxicity through inhibition of endoplasmic reticulum stress - Xiu-Yu Wang; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Ai-Ping Lan; Zhan-Li Yang; Fen Hu; Pei-Xi Chen; Xin-Xue Liao; Jian-Qiang Feng (Molecular and Cellular Biochemistry, 2012)

Fertilization increases paddy soil organic carbon density - Shao-xian Wang; Xin-qiang Liang; Qi-xiang Luo; Fang Fan; Ying-xu Chen; Zu-zhang Li; Huo-xi Sun; Tian-fang Dai; Jun-nan Wan; Xiao-jun Li (Journal of Zhejiang University-SCIENCE B, 2012)

Inhibition of ROS-activated ERK1/2 pathway contributes to the protection of H2S against chemical hypoxia-induced injury in H9c2 cells - Xiao-Bian Dong; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Xiu-Yu Wang; Ai-Ping Lan; Fen Hu; Pei-Xi Chen; Jian-Qiang Feng; Mei-Fen Zhang; Xin-Xue Liao (Molecular and Cellular Biochemistry, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

A risk-associated single nucleotide polymorphism of SMAD7 is common to colorectal, gastric, and lung cancers in a Han Chinese population - Xin Li; Xue-xi Yang; Ni-ya Hu; Jing-zhe Sun; Fen-xia Li; Ming Li (Molecular Biology Reports, 2011)

Genetic differentiation and phylogeographical structure of the Brachionus calyciflorus complex in eastern China - XIAN‐LING XIANG; YI‐LONG XI; XIN‐LI WEN; GEN ZHANG; JIN‐XIA WANG; KE HU (Molecular Ecology, 2011)
Spatio‐temporal patterns and processes of genetic differentiation in passively dispersing zooplankton are drawing much attention from both ecologists and evolutionary biologists. Two opposite phylogeographical scenarios have already been demonstrated in rotifers, which consist of high levels of genetic differentiation among populations even on small geographical scales on the one hand and the traditionally known cosmopolitanism that is associated with high levels of gene flow and long‐distance dispersal via diapausing stages on the other hand. Here, we analysed the population genetic structure and the phylogeography of the Brachionus calyciflorus species complex in eastern China. By screening a total of 318 individuals from ten locations along a 2320‐km gradient and analysing samples from two growing seasons, we aimed at focusing on both small‐ and large‐scale patterns. We identified eight cryptic species and verified species status of two of these by sexual reproduction tests. Samples in summer and winter yielded different cryptic species. The distribution patterns of these genetically distinct cryptic species were diverse across eastern China, from full cosmopolitanism to local endemism. The two most abundant cryptic species BcWIII and BcSW showed a pattern of strong genetic differentiation among populations and no significant isolation by distance. Long‐distance colonization, secondary contact and recent range expansion are probably responsible for the indistinct pattern of isolation by distance. Our results suggest that geographical distance is more important than temporal segregation across seasons in explaining population differentiation and the occurrence of cryptic species. We explain the current phylogeographical structure in the B. calyciflorus species complex by a combination of recent population expansion, restricted gene flow, priority effects and long‐distance colonization.

The mechanisms underlying ICa heterogeneity across murine left ventricle - Lin Xu; Xu-Yong Li; Yu Liu; Hai-Tao Li; Jing Chen; Xiao-Yan Li; Xue-Jun Jiang; Gang Wu; Yan-Hong Tang; Xi Wang; Cong-Xin Huang (Molecular and Cellular Biochemistry, 2011)

BRAF V600E mutation and resistance to anti-EGFR monoclonal antibodies in patients with metastatic colorectal cancer: a meta-analysis - Chen Mao; Ru-Yan Liao; Li-Xin Qiu; Xi-Wen Wang; Hong Ding; Qing Chen (Molecular Biology Reports, 2011)

Comparative analysis of rotifer community structure in five subtropical shallow lakes in East China: role of physical and chemical conditions - Xin-Li Wen; Yi-Long Xi; Fang-Ping Qian; Gen Zhang; Xian-Ling Xiang (Hydrobiologia, 2011)

osa-MIR393: a salinity- and alkaline stress-related microRNA gene - Peng Gao; Xi Bai; Liang Yang; Dekang Lv; Xin Pan; Yong Li; Hua Cai; Wei Ji; Qin Chen; Yanming Zhu (Molecular Biology Reports, 2011)

Effect of enalapril on plasma homocysteine levels in patients with essential hypertension - Fang-fang Fan; Yong Huo; Xu Wang; Xin Xu; Bin-yan Wang; Xi-ping Xu; Jian-ping Li (Journal of Zhejiang University-SCIENCE B, 2010)

Two new naphthylisoquinoline alkaloids from stems and leaves of Ancistrocladus tectorius - Chun-Ping Tang; Zhen-Qiang Xin; Xi-Qiang Li; Yang Ye (Natural Product Research, 2010)

Arachnoid cell involvement in the mechanism of coagulation-initiated inflammation in the subarachnoid space after subarachnoid hemorrhage - Zhao-liang Xin; Xiao-kang Wu; Jian-rong Xu; Xi Li (Journal of Zhejiang University-SCIENCE B, 2010)

Potential water sources for Late Quaternary Megalake Jilantai-Hetao, China, inferred from mollusk shell 87Sr/86Sr ratios - Yu-Xin Fan; Fa-Hu Chen; Guo-Xiao Wei; David B. Madsen; Charles G. Oviatt; Hui Zhao; Xi Chun; Li-Ping Yang; Tian-Lai Fan; Guo-Qiang Li (Journal of Paleolimnology, 2010)

Simvastatin attenuates TNF-α-induced growth inhibition and apoptosis in murine osteoblastic MC3T3-E1 cells - Yun-mei Yang; Wei-dong Huang; Qiang-min Xie; Zhe-rong Xu; Qi-jiang Zhao; Xi-mei Wu; Fen-fen Li; Xin-wei Dong (Inflammation Research, 2010)

FAK is involved in invasion and metastasis of hepatocellular carcinoma - Jing-Song Chen; Xiao-Hui Huang; Qian Wang; Xi-Lin Chen; Xin-Hui Fu; Hao-Xiang Tan; Long-Juan Zhang; Wen Li; Jiong Bi (Clinical & Experimental Metastasis, 2010)

Spatial patterns of genetic differentiation in Brachionus calyciflorus species complex collected from East China in summer - Xian-Ling Xiang; Yi-Long Xi; Xin-Li Wen; Jin-Yan Zhang; Qin Ma (Hydrobiologia, 2010)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

The effects of mesenchymal stem cells on c-kit up-regulation and cell-cycle re-entry of neonatal cardiomyocytes are mediated by activation of insulin-like growth factor 1 receptor - Xi-Yong Yu; Yong-Jian Geng; Xiao-Hong Li; Qiu-Xiong Lin; Zhi-Xin Shan; Shu-Guang Lin; Yao-Hua Song; Yangxin Li (Molecular and Cellular Biochemistry, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

TM4SF3 promotes esophageal carcinoma metastasis via upregulating ADAM12m expression - Zhuan Zhou; Yu-Liang Ran; Hai Hu; Jian Pan; Zhi-Feng Li; Li-Zhao Chen; Li-Chao Sun; Liang Peng; Xi-Lu Zhao; Long Yu; Li-Xin Sun; Zhi-Hua Yang (Clinical & Experimental Metastasis, 2008)

Arbuscular mycorrhizal status of plants and the spore density of arbuscular mycorrhizal fungi in the tropical rain forest of Xishuangbanna, southwest China - Zhi-Wei Zhao; Yong-Mei Xia; Xin-Zheng Qin; Xi-Wu Li; Li-Zhong Cheng; Tao Sha; Guo-Hua Wang (Mycorrhiza, 2001)